Structured machine learning modeling to support conservation of deep‐sea benthic biodiversity - Gustavo Fonseca; Danilo C. Vieira; Juliane C. Carneiro; Renato S. Carreira; Milena Ceccopieri; Thais N. Corbisier; Adriana Galindo Dalto; Alberto G. Figueiredo; Fabiane Gallucci; Paula Gheller; Simone Brito de Jesus; Helena Passeri Lavrado; et al. (Conservation Biology, 2026)
Biodiversity monitoring programs need to deliver accurate, timely, and actionable predictions. To establish a predictive monitoring program for deep‐sea benthos of the Santos Basin, Brazil, we developed a two‐stage structured model that allowed comparison of biodiversity predictions obtained from environmental simulations (2M‐Sim). We also modeled the environmental variables as a function of spatial and temporal variables and compared this model's predictions with predictions obtained from real environmental data (2M). We built unstructured models (1M) as references to evaluate whether the proposed structured approach was reliable. We expected no significant differences between 1M and 2M or between 2M and 2M‐Sim. Data were obtained from 100 stations at depths of 25–2400 m during two surveys (2019 and 2021). In our model framework, we used 12 benthic macro‐ and meiofaunal variables, 44 sediment and water column environmental variables, and four spatial and temporal variables. We applied a random forest algorithm to the structured and unstructured models. All comparisons were performed with 20% of the dataset set aside for validation. The average accuracy was 72%, 69%, and 68% for the 1M, 2M, and 2M‐Sim models, respectively. Accuracies of 2M ranged from 38% to 84% and were generally higher for macrofauna. The observed accuracy loss from 1M to 2M (3%) and from 2M to 2M‐Sim (1%) was not significant for any biodiversity variable. The 2M model identified 30 significant environmental variables; bottom water parameters and sedimentary phytopigment and carbonate concentrations were the best predictors. Our approach supports biodiversity conservation by optimizing data needs and future sampling and by guiding data‐driven management decisions for benthic biodiversity.

Geometry, spin coupling, and dielectric control of redox potentials in [4Fe–4S] Clusters - Peter S. Rice; Bruno Jacob; Khushbu Agarwal; Marcel D. Baer; Simone Raugei (JBIC Journal of Biological Inorganic Chemistry, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Thiazolidinedione-triazole hybrids: design, synthesis, and biological evaluation as dual inhibitors of α-amylase and aldose reductase with antioxidant activity for antidiabetic therapy - Eman E. Nasr; Mohamed R. Elnagar; Nahed Nasser Eid El-Sayed; Marwa I Serag; Mostafa M. Elbadawi; Adel S. El-Azab; Simone Brogi; Hazem A. Ghabbour; Abdelrahman Hamdi; Alaa A.- M. Abdel-Aziz (Molecular Diversity, 2026)

From dive slates to digital imagery: an evaluation of the effect of coral reef assessment methods on benthic and substrate compositions and an alignment between methods - Tri A. Hadi; Ian R. Tibbetts; Giyanto; Novi S. Adi; Peter J. Mumby; Simone P. Blomberg (Coral Reefs, 2026)
Various underwater survey methods have been used for coral reef assessment and long-term monitoring; however, comparing data across different methods remains challenging and can obscure ecological patterns. This study compared and aligned three commonly used survey methods in Indonesia, including line-intercept transects (LIT) and point-intercept transects (PIT) recorded on dive slates, and underwater photo transects (UPT), to improve data consistency and comparability. Surveys were conducted at 56 sites across four locations between 2013 and 2014. Two Bayesian Dirichlet models were fitted. The first model assessed the relative performance of the methods while accounting for random effects (location and site within location). The results indicated that UPT generally produced higher estimated per cent cover across most benthic and substrate categories; PIT was typically intermediate; and LIT tended to yield lower estimates for most categories, while relatively overestimating hard coral cover compared with UPT. Because of these discrepancies, the second model was developed to convert LIT or PIT data into UPT-equivalent compositions. While the predictive models have limitations, the predictions for most categories were relatively reliable and, in general, statistically indistinguishable from the observed UPT data, especially at the community level. These models can be iteratively refit to improve regional generalisability by adding observations from different sites and locations, or applied to new sites and locations by excluding the random effect at the cost of increased uncertainty. Overall, this approach improves data comparability and consistency, supporting long-term monitoring and conservation efforts by making conventional and modern methods more directly comparable.

Groundwater inflow into tunnels: semi-empirical methods for estimating steady state inflow associated with excavation induced drawdown - Simone L. Markus; Mark S. Diederichs (Tunnelling and Underground Space Technology, 2026)

Quinazoline-sulfonamide hybrids as multitarget anticancer agents: inhibition of carbonic anhydrase IX/XII isoforms and VEGFR-2 with in vitro and in silico validation - Mohamed A. Zeidan; Mohammad M. Al-Sanea; Mohamed R. Elnagar; Mohamed M. Tawfik; Hamed W. El-Shafey; Samar S. Tawfik; Simone Brogi; Abdelrahman Hamdi (Molecular Diversity, 2026)

Non-native mollusc species in Brazil: a first national inventory and distributional overview - Fabrizio Marcondes Machado; Rodrigo B. Salvador; Igor C. Miyahira; Luiz Ricardo Lopes de Simone; Tarcilla C. de Lima; Mariana Osório Côrtes; Julia D. Sigwart; Angie Patiño Montoya; Vanessa S. Amaral; Paula Spotorno; Marcel Sabino Miranda; Augusto L. Ferreira Júnior; et al. (Biological Invasions, 2026)

The role of modifiable risk factors on the cerebral myelin content and cognition: findings from The Maastricht Study - Gerhard S. Drenthen; Walter H. Backes; Sebastian Köhler; Kay Deckers; Miranda T. Schram; Simone J. P. M. Eussen; Willemijn J. Jansen; Jacobus F. A. Jansen (GeroScience, 2026)
Lifestyle-related factors may affect cognition and increase the risk of developing dementia. However, the neurobiological mechanisms underlying the effect of lifestyle-related factors on the brain are not yet fully understood. Myelin, a vital element of brain health, has previously been shown to be involved in dementia-related cognitive decline. However, whether it plays a role in the relation between lifestyle-related factors and cognitive performance has not been studied. The cerebral myelin content of 4653 participants (51% female, aged 59 ± 9 years) from The Maastricht Study was estimated using the T1w/FLAIR-ratio, and lifestyle-related factors were summarized using the LIBRA-score. Multivariable linear regression models, corrected for the effects of age, sex and education, were used to investigate whether lifestyle-related factors are associated with myelin. Moreover, whether myelin can partly explain the relationship between lifestyle-related factors and cognition was explored using a mediation analysis across three cognitive domains (memory, executive functioning and processing speed). An unhealthy lifestyle (i.e. higher LIBRA score) is significantly associated to a lower cerebral myelin content ( β = −0.24, 95% CI [−0.26 −0.22], and p < 0.001). Furthermore, lower cerebral myelin content associates to worse cognitive performance ( β = 0.14, 95% CI [0.11 0.17], and p < 0.001). Moreover, myelin has a partially mediating effect of 15%, indicating that it partly explains the relation between lifestyle-related factors and cognition. These results show that myelin content might help explain the mechanisms through which lifestyle-related factors influence cognition, potentially allowing for specific and early lifestyle interventions aimed at preventing or delaying cognitive decline and dementia. Graphical abstract

Dendropsophin 1, an antimicrobial peptide from skin secretion of the tree frog Dendropsophus columbianus, exhibits tissue repair potential - Isabella S. Cassimiro; Bruno A. Ferreira; Simone R. Deconte; Taís C. Lima; Francyelle B.R. Moura; Mariana S. Castro; Fernanda A. Araújo (Toxicon, 2026)

Enhanced forest structural heterogeneity increases functional β-diversity but reduces α- and γ-diversity in soil nematodes - Rike Schwarz; Pia M. Bradler; Anne Chao; Po-Yen Chuang; Marcel Ciobanu; Orsi Decker; Benjamin M. Delory; Peter Dietrich; Sebastian Dittrich; Andreas Fichtner; Ludwig Lettenmaier; Michael Junginger; et al. (Soil Biology and Biochemistry, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Two-phase leakage detection strategy supported by district metering areas - G. Messa; G. Acconciaioco; S. Ripani; L. Bozzelli; A. Simone; O. Giustolisi (Journal of Water Process Engineering, 2026)

Layered zinc hydroxide–dipeptide hybrid integrated into silk-based 3D scaffolds aiming for biomedical applications - Denise Eulálio; Mariana Pires Figueiredo; Simone S. Silva; Luísa C. Rodrigues; Emanuel M. Fernandes; Albino Martins; Albina Franco; Diana Soares da Costa; Richard Landers; Fabrice Leroux; Christine Taviot-Gueho; Dalva Lúcia Araújo de Faria; et al. (Applied Clay Science, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Coral health status before and after the tourism halt caused by the COVID-19 pandemic in Koh Tao (Thailand) - Matilde Baruffaldi; Camilla Roveta; Elouise S. Haskin; Simone Fazio; Chad Scott; Kirsty Magson; Cristina Gioia Di Camillo (Coral Reefs, 2026)

Replacing Conventional Fertilization with Organomineral Fertilizer in ‘Hass’ Avocado Trees Improves Chlorophyll Indices and Fruit Size: A Bootstrap Simulation Approach - Marllon F. S. dos Santos; Rodrigo J. Milan; Bruna M. Costa; Tatiana E. Cantuarias-Avilés; Idemauro A. R. de Lara; Simone R. da Silva (Applied Fruit Science, 2026)
Modern agriculture faces significant challenges related to the depletion of finite resources used in fertilizer production. In response to this situation, the market has been adapting by developing biofertilizers or organomineral fertilizers, which incorporate an organic fraction into their composition. These fertilizers provide nutrients more gradually, reducing leaching. Studies on this topic are scarce for avocado trees, whose global production has been increasing. For this reason, the present research aimed to compare conventional fertilization with organomineral fertilization in ‘Hass’ avocado trees. A total of 20 plants per treatment were used in a commercial orchard, with treatments providing the same amount of nutrients. Variables related to vegetative growth, gas exchange, and productive data were evaluated. Data analysis was performed using bootstrap simulations, a resampling technique with 10,000 simulations, which enabled the construction of confidence intervals for the variables being assessed, resulting in an experimental optimization. Although no significant differences were detected in overall yield, the organomineral treatment showed increases of up to 10% in chlorophyll levels, 17.69% in fruit weight, and 8.35% and 9.18% in fruit length and diameter, respectively, compared to the conventional treatment. The bootstrap technique proved effective for analyzing this type of experiment, confirming the benefits of replacing conventional fertilization with organomineral fertilization, which provides nutrients more efficiently and sustainably.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

A summary of the Lucy Ashton resistance prediction workshop - Rui Lopes; Arash Eslamdoost; Rickard E. Bensow; Dmitriy Ponkratov; Anja Kömpe; Paolo Geremia; Çagan Birant Pekküçük; Cagri Aydin; Diego Villa; Dimitris Ntouras; Dong Cheol Seo; Gennaro Rosano; et al. (Ocean Engineering, 2026)

Assessing the influence of morphological variability and classifier arrangement on tandem particle classification analysis - Joshua S. Hassim; Simone Hochgreb; Adam M. Boies (Journal of Aerosol Science, 2026)

In vitro methods for evaluation of sulfur mustard on cell senescence - S. Emma Sarles; Adrian Neu; Linda N. Pettersson; Tobias Demel; Priscilla Lee; Daniel Angelini; Simone Rothmiller; Dirk Steinritz (Chemico-Biological Interactions, 2026)

Genesis of the hot spring mercury deposits of the Mt. Amiata geothermal system (Italy) constrained by Hg and S isotope geochemistry - Paolo S. Garofalo; Farshid Kiani; Andrea Marchetti; Lisa Lancellotti; Orlando Vaselli; Simone Beccari; Gaetano Pedone; Daniele Rappuoli (Mineralium Deposita, 2026)
The world-class geothermal system of Mt. Amiata, Italy, comprises a district of 14 hot-spring cinnabar ± stibnite deposits. We determined the Hg isotopic compositions of cinnabar and basement rocks of the geothermal system, coupled with S isotopic compositions of cinnabar, marcasite and stibnite, to constrain the source rocks in this geological environment. Most cinnabar, stibnite, and marcasite samples have δ 34 S between − 0.9 and + 5‰. Cinnabar shows a relatively large range of δ 202 Hg from − 3.64 to + 0.17‰ and Δ 199 Hg from − 0.43 to + 1.06‰, although samples from individual deposits show much narrower δ 202 Hg ranges. We interpret these values as the products of hydrothermal fractionation and mixing of magmatic, metamorphic, and marine sedimentary sources of Hg (Sb) and S, from which the samples inherited their signature. Comparison between the Hg isotopic signatures of the Mt. Amiata cinnabar and those of the world-class submarine geothermal systems of Almadén (Spain) and Idrija (Slovenia) shows significant differences. At Almadén and Idrija, the range of δ 202 Hg values are typically < 2‰, while the corresponding values for Mt. Amiata have a much larger spread, similar to other geothermal systems in the western USA. This indicates notable differences between the range of fractionation processes occurring in submarine and continental geothermal systems.

Mapping the landscape of mycological organizations in europe: where citizen science meets professional mycology - Danny Haelewaters; Dilzara Aghayeva; Sergio de-Miguel; Polina Degtjarenko; Glen Dierickx; Bálint Dima; Paul S. Dyer; Vasco Fachada; Sergio Enrico Favero-Longo; Nina V. Filippova; Montserrat Ganado; Susana C. Gonçalves; et al. (Biodiversity and Conservation, 2026)
Fungi have been used by humans since prehistoric times. Informal structures or groups for knowledge exchange regarding mushrooms and lichens probably existed for ages. Only recently, mycological activities have been structured in formal organizations. And where until a few centuries ago there were only learned societies and naturalists’ clubs, nowadays also mycological societies and citizen scientists have joined the landscape. However, the history of mycological organizations and activities in Europe is difficult to track. Here, we initiated two surveys to characterize the current landscape of mycological organizations focused on fungal diversity across Europe and to collate citizen science activities mapping fungi. The surveys were shared on social media and sent to mycologists in 49 countries in Europe. Responses of the surveys allowed us to present the history, geographical distribution, and structure of mycological organizations in Europe as well as their types of activities, including the publication of journals and magazines, the organization of meetings and educational initiatives, and citizen science projects. In addition to the surveys, local mycologists presented expert knowledge for a more comprehensive overview. Our data show that the mycological landscape in Europe is diverse and heterogeneous. We discuss ways to overcome economic, cultural, and linguistic barriers towards better integration of mycological communities, activities, and data in Europe. Mycological societies focused on studying fungal diversity can be leveraged towards common goals that include raising public awareness, data integration, uniting academics and non-academics, and developing common standards for research and communication.

Vegetation type and climate determine temperature thresholds of soil respiration across drylands - María Almagro; Ana Rey; Rosa M. Inclán; Josep Barba; Rodrigo Vargas; Arnaud Carrara; José M. Grünzweig; Marcelo Sternberg; Yiftach Talmon; Rebecca L. McCulley; Sara Marañón-Jiménez; Penélope Serrano-Ortiz; et al. (Soil Biology and Biochemistry, 2025)

The microbiome’s hidden influence: preclinical insights into inflammatory responses in necrotizing enterocolitis - Briana M. Peterson; Ina Rudloff; Nadia S. Deen; Sara K. Di Simone; Ramesh M. Nataraja; Gergely Toldi; Maurizio Pacilli; Steven P. Garrick; Steven X. Cho; Marcel F. Nold; Samuel C. Forster; Claudia A. Nold-Petry (Seminars in Immunopathology, 2025)
Necrotizing enterocolitis (NEC) is the most common surgical emergency in preterm infants; nonetheless, besides supportive measures, no treatment is available. NEC significantly increases length of hospitalization of preterm infants, causes severe morbidity and up to 70% mortality. Despite limited understanding of the underlying mechanisms, prematurity, dysbiosis and an underdeveloped immune system are known to increase the risks of developing NEC. The low weight of preterm infants (often < 2000 g) and unpredictable progression of NEC hinder clinical research; hence, most of our mechanistic understanding of NEC pathophysiology has arisen from animal models. Recent advances in bacterial genomic analyses highlighted the intestinal microbiome’s key role in NEC, strengthening the concept that this disease results from an interaction between the patient’s developing immune system and their microbiome. This notion is supported by the moderate effect of probiotics in preventing NEC. Here, we review the current knowledge on how the immune system interacts with the intestinal microbiome in early life, including in relation to NEC, describe the current evidence from cohort studies, clinical trials, in vivo and in vitro models used to study NEC, and methods to modulate the immune system and microbiome in early life. Knowledge on the early-life microbiome and immune system in health and diseases, including NEC, can be harnessed to develop novel and urgently needed immunomodulatory and microbiota-based therapeutics.

Limosilactobacillus reuteri UN41 improves the survival rate and exhibits hepatoprotective effects in a murine model of Salmonella infection - Melina A. Cordeiro; Vivian C. Miranda; Katharina O. Barros; Paulo H. F. Carmo; Luísa M. Trindade; Simone O. A. Fernandes; Valbert N. Cardoso; Rosa M. E. Arantes; Mayra F. Ricci; Silvia B. Moura; Flaviano S. Martins (Brazilian Journal of Microbiology, 2025)

Food-grade titanium dioxide exposure between age groups and in global regions: a systematic review and meta-analysis - Nicolaj S. Bischoff; Marina R. Bussi; Simone G. Van Breda; Shahab Jolani; Dick T. H. M. Sijm; Theo M. de Kok; Jacco J. Briedé (Critical Reviews in Food Science and Nutrition, 2025)

Fibronectin recognition by the emerging multidrug-resistant opportunistic fungal pathogen Candida haemulonii - Lívia S. Ramos; Thaís P. Mello; Lucas B. Magalhães; Laura N. Silva; Simone S. C. Oliveira; Marta H. Branquinha; André L. S. Santos (Folia Microbiologica, 2025)

Global Patterns and Drivers of Seagrass Biomass, Net Primary Production and Meadow Structure - Nicole R. Foster; Enric Gomis; Diana I. Montemayor; Simone Strydom; Miguel Angel Mateo; Eduard Serrano; Aurora M. Ricart; Martin Dahl; Ines Mazarrasa; Paulina Cisternas; Harry Whiteley; Elliott J. Bates; et al. (Journal of Biogeography, 2025)
Aim We decipher global patterns in seagrass growth and structure to advance seagrass science, facilitate multidisciplinary research, and promote effective management strategies and policy development for seagrass habitats. Location: Global. Time period: 1975 to 2024. Major taxa studied: Seagrasses—marine angiosperms. Methods A global data set on seagrass total biomass, total net primary productivity (NPP), shoot density, and percent cover was compiled across 11 genera. We tested how these variables change across seagrass genera, life‐history strategy, and geographic location; and then modelled the environmental drivers (temperature, nutrients, light availability) of the patterns observed. Results The mean (±SE) total biomass of seagrasses globally was estimated at 340 ± 10 g DW m −2 and total NPP was estimated at 5.4 ± 0.4 g DW m −2 d −1 . Mean shoot density across all genera was 1,780 ± 67 shoots m −2 and percent cover was 42% ± 1%. Persistent genera showed the highest total biomass followed by opportunistic then colonising genera, whereas shoot density was higher for colonising than persistent, which had the highest percent cover. Latitudinal and bioregional patterns were identified for some genera and were mostly driven by genus‐specific traits, followed by localised environmental factors. Main Conclusions Trends in seagrass meadow ecology were largely influenced by seagrass genera and their life‐history strategy, with localised environmental factors, such as temperature and nutrients, also playing a role. Global estimates of seagrass biomass and NPP were 2‐times higher than previously reported. Seagrass life‐history strategies modulate the trade‐offs between NPP and biomass to thrive in specific habitats. This study provides the most updated global synthesis of patterns in seagrass growth and structure.

E171-induced toxicity in human iPSC-derived colon organoids: Effects on cell viability, ROS generation, DNA damage, and gene expression changes - Nicolaj S. Bischoff; Anna K. Undas; Marcel van Herwijnen; Marcha Verheijen; Jacco J. Briedé; Simone G. van Breda; Dick T.H.M. Sijm; Theo M. de Kok (Toxicology in Vitro, 2025)

Iron, manganese, and copper complexes protect saccharomyces cerevisiae from methyl methanesulfonate-induced genotoxicity and oxidative stress - Larissa M. M. Mattos; Davi A. Andrade; Alan N. S. Alves; Victória T. Ferreira; Simone S. C. Oliveira; Bruna B. Segat; André L. S. Santos; Adolfo Horn; Christiane Fernandes; Marcos D. Pereira (World Journal of Microbiology and Biotechnology, 2025)

Correction: Diego-Tortosa et al. Effective Strategies for Automatic Analysis of Acoustic Signals in Long-Term Monitoring. J. Mar. Sci. Eng. 2025, 13, 454 - Dídac Diego-Tortosa; Danilo Bonanno; Manuel Bou-Cabo; Letizia S. Di Mauro; Abdelghani Idrissi; Guillermo Lara; Giorgio Riccobene; Simone Sanfilippo; Salvatore Viola (Journal of Marine Science and Engineering, 2025)
There was an error in the original publication [...]

Ontogeny unlocks the floral development and evolution of Uleanthus, a florally divergent monospecific genus of Amazonian legume trees - Catarina S. Carvalho; Gerhard Prenner; Simone Pádua Teixeira; Thiago André; Annícia Barata; Charles E. Zartman; Domingos Cardoso (Perspectives in Plant Ecology, Evolution and Systematics, 2025)

Power- and biomass-to-liquid processes with fuel-assisted solid oxide electrolysis cells and water gas shift-adjusted systems: A techno-economic analysis - Samuel M. Krämer; Anders S. Nielsen; Simon Maier; Simone Mucci; Magne Hillestad; Odne S. Burheim (Fuel, 2025)

Diversity in Resource Use Strategies Promotes Productivity in Young Planted Tree Species Mixtures - Joel Jensen; Haben Blondeel; Joannès Guillemot; Florian Schnabel; Hernán Serrano‐León; Harald Auge; Lander Baeten; Nadia Barsoum; Jürgen Bauhus; Christel Baum; Raimundo Bermudez; Friderike Beyer; et al. (Global Change Biology, 2025)
Mixed‐species forestry is a promising approach to enhance productivity, increase carbon sequestration, and mitigate climate change. Diverse forests, composed of species with varying structures and functional trait profiles, may have higher functional and structural diversity, which are attributes relevant to a number of mechanisms that can influence productivity. However, it remains unclear whether the context‐dependent roles of functional identity, functional diversity, and structural diversity can lead to a generalized understanding of tree diversity effects on stand productivity. To address these gaps, we analyzed growth data from 83,600 trees from 89 species across 21 young tree diversity experiments spanning five continents and three biomes. Results revealed a positive saturating relationship between tree species richness and stand productivity, with reduced variability in growth rates among more diverse stands. Structural equation modeling demonstrated that functional diversity mediated the positive effects of species richness on productivity. We additionally report a negative relationship between structural diversity and productivity, which decreased with increasing species richness. When partitioning net diversity effects, we found that selection effects played a dominant role in driving the overall increase in productivity in these predominantly young stands, contributing 77% of the net diversity effect. Selection effects increased with diversity in wood density. Furthermore, acquisitive species with lower wood density and higher leaf nitrogen content had higher productivity in more diverse stands, while conservative species showed neutral to slightly negative responses to species mixing. Together, these results suggest that combining acquisitive with conservative species allows acquisitive species to drive positive selection effects while conservative species tolerate competition. Thus, contrasting resource‐use strategies can enhance productivity to optimize mixed‐species forestry, with potential for both ecological and economic benefits.

Borealisation of Plant Communities in the Arctic Is Driven by Boreal‐Tundra Species - Mariana García Criado; Isabel C. Barrio; James D. M. Speed; Anne D. Bjorkman; Sarah C. Elmendorf; Isla H. Myers‐Smith; Rien Aerts; Juha M. Alatalo; Katlyn R. Betway‐May; Robert G. Björk; Mats P. Björkman; Daan Blok; et al. (Ecology Letters, 2025)
Following rapid climate change, tundra plant communities are experiencing extensive compositional shifts. A conservation concern is the potential encroachment of boreal species into the tundra (‘borealisation’). Tundra borealisation has been sporadically reported, but not systematically quantified. Here, we synthesised data from across 32 study areas, spanning 1137 plots and 287 vascular plant species, resurveyed between 1981 and 2023. We (i) quantified tundra borealisation as the colonisation and increase in abundance of Boreal and Boreal‐Tundra species, (ii) assessed biogeographical, climatic and local borealisation drivers and (iii) identified species contributing to borealisation and their associated traits. Half of the plots experienced borealisation, although borealisation rates were not different to random expectation. Borealisation was greater in Eurasia, closer to the treeline, at higher elevations, in warmer and wetter regions, where climate change was limited, and where initial boreal abundance was lower. Boreal coloniser species were generally short‐statured, and more often shrubs and graminoids. Boreal species colonised around three times less frequently than Boreal‐Tundra species. Hence, our findings indicate that tundra borealisation is mainly driven by the spread of already established boreal‐low Arctic tundra species. These plant community composition changes could have cascading impacts on land‐atmosphere interactions, trophic dynamics and Indigenous and local livelihoods.

A CSF-1R inhibitor both prevents and treats triple-negative breast cancer brain metastases in hematogenous preclinical models - Wei Zhang; Samiur Rahman; Alex M. L. Wu; Kristine Isanogle; Christina Robinson; Dinesh Kumar; Imran Khan; Debbie Wei; Alexandra S. Zimmer; Takeo Fujii; Simone Difilippantonio; Stanley Lipkowitz; et al. (Clinical & Experimental Metastasis, 2025)
Brain metastasis is a common and serious complication of metastatic triple-negative breast cancer (TNBC) with few effective treatments. Here, we evaluated the effect of targeting the brain tumor microenvironment via the myeloid colony-stimulating factor-1 receptor (CSF-1R) pathway using the small molecule inhibitor BLZ945. Studies were conducted in two TNBC hematogenous brain-tropic models, 4T1-BR5 and 231-BR, with endpoints of prevention of brain metastasis formation and treatment of established brain metastasis. BLZ945 reduced the formation of brain metastases in both models by 57–65% (all p < 0.01) in the prevention setting. In the treatment setting, more analogous to the clinical situation, BLZ945 reduced the number and size of metastases in both models by 44–65% and 61–72%, respectively (all p < 0.05). Treatment with BLZ945 significantly reduced the number of myeloid cells in both the uninvolved brain and metastatic regions, by 15–54% across models as early as three days post-treatment. Efficacy was achieved without the need for complete suppression of brain myeloid cells, suggesting that potential adverse effects of full myeloid suppression can be minimized. Additionally, BLZ945 reduced cancer cell proliferation and astrocyte activation in the tumor microenvironment in vivo . In vitro studies showed that BLZ945 inhibited the secretion of inflammatory cytokines that stimulated cancer cell invasion; BLZ945 also indirectly reduced cancer cell proliferation through astrocyte interaction. Our findings suggest that microglial CSF-1R controls a series of myeloid regulatory pathways, both alone and in concert with other brain microenvironmental cells. The data preclinically credential CSF-1R inhibition as a potential therapeutic strategy for TNBC brain metastases.

Post-weaning exposure to cannabidiol disrupts testicular cytoarchitecture and sperm quality in mice - Renata K. Carvalho; Maingredy R. Souza; Akemy N. Nishimura; Edvaldo M. Silva; Cinthia R.B. Silva; Francisco S. Guimarães; Monica L. Andersen; Simone M.T. Sabóia-Morais; Renata Mazaro-Costa (Reproductive Toxicology, 2025)

Oral Treatment with Saccharomyces cerevisiae CNCM I-3856 Mitigates the Inflammatory Response Experimentally Induced by Salmonella enterica subsp. enterica Serovar Typhimurium in Mice - Lara L. Campos; Samantha R. M. Oliveira; Maisa N. S. Amaral; Bruno Gallotti; Aline F. Oliveira; Rosa M. E. Arantes; Samantha Ribeiro-Souza; Katia D. Vital; Simone O. A. Fernandes; Valbert N. Cardoso; Jacques R. Nicoli; Flaviano S. Martins (Probiotics and Antimicrobial Proteins, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Could Exotic Birds Play a Significant Role in the Emergence of Antibiotic-Resistant Microorganisms? - Gabriel H. S. Britto; Lara R. Gomes; João P. Pimenta; Simone Sommerfeld; Maysa V. C. Silva; Phelipe A. B. M. Peres; Paula F. S. Braga; Letícia R. M. Costa; Isabelle E. Pedrosa; Márcio B. Bandarra; Terezinha Knöbl; Belchiolina B. Fonseca (Current Microbiology, 2025)

Sustainable Land Use Enhances Soil Microbial Respiration Responses to Experimental Heat Stress - Rémy Beugnon; Nico Eisenhauer; Alfred Lochner; Margarete J. Blechinger; Paula E. Buhr; Simone Cesarz; Monica A. Farfan; Olga Ferlian; Amanda J. Rompeltien Howard; Yuanyuan Huang; Blanca S. Kuhlmann; Nora Lienicke; et al. (Global Change Biology, 2025)
Soil microbial communities provide numerous ecosystem functions, such as nutrient cycling, decomposition, and carbon storage. However, global change, including land‐use and climate changes, affects soil microbial communities and activity. As extreme weather events (e.g., heatwaves) tend to increase in magnitude and frequency, we investigated the effects of heat stress on the activity (e.g., respiration) of soil microbial communities that had experienced four different long‐term land‐use intensity treatments (ranging from extensive grassland and intensive grassland to organic and conventional croplands) and two climate conditions (ambient vs. predicted future climate). We hypothesized that both intensive land use and future climate conditions would reduce soil microbial respiration (H1) and that experimental heat stress would increase microbial respiration (H2). However, this increase would be less pronounced in soils with a long‐term history of high‐intensity land use and future climate conditions (H3), and soils with a higher fungal‐to‐bacterial ratio would show a more moderate response to warming (H4). Our study showed that soil microbial respiration was reduced under high land‐use intensity (i.e., −43% between extensive grassland and conventional cropland) and future climate conditions (−12% in comparison to the ambient climate). Moreover, heat stress increased overall microbial respiration (+17% per 1°C increase), while increasing land‐use intensity reduced the strength of this response (−25% slope reduction). In addition, increasing soil microbial biomass and fungal‐to‐bacterial ratio under low‐intensity land use (i.e., extensive grassland) enhanced the microbial respiration response to heat stress. These findings show that intensive land use and climate change may compromise the activity of soil microbial communities as well as their respiration under heatwaves. In particular, soil microbial communities under high‐intensity land use and future climate are less able to respond to additional stress, such as heatwaves, potentially threatening the critical ecosystem functions driven by soil microbes and highlighting the benefits of more sustainable agricultural practices.

Detection of Seismic and Acoustic Sources Using Distributed Acoustic Sensing Technology in the Gulf of Catania - Abdelghani Idrissi; Danilo Bonanno; Letizia S. Di Mauro; Dídac Diego-Tortosa; Clara Gómez-García; Stephan Ker; Florian Le Pape; Shane Murphy; Sara Pulvirenti; Giorgio Riccobene; Simone Sanfilippo; Salvatore Viola (Journal of Marine Science and Engineering, 2025)
Distributed Acoustic Sensing (DAS) technology presents an innovative method for marine monitoring by adapting existing underwater optical fiber networks. This paper examines the use of DAS with the Istituto Nazionale di Fisica Nucleare–Laboratori Nazionali del Sud (INFN-LNS) optical fiber infrastructure in the Gulf of Catania, Eastern Sicily, Italy. This region in the Western Ionian Sea provides a unique natural laboratory due to its tectonic and volcanic activity, proximity to Mount Etna, diverse marine ecosystems and significant human influence through maritime traffic. By connecting a 28 km long optical cable to an Alcatel Submarine Network OptoDAS interrogator, DAS successfully detected a range of natural and human–made signals, including a magnitude 3.5 ML earthquake recorded on 14 November 2023, and acoustic signatures from vessel noise. The earthquake–induced Power Spectral Density (PSD) increased to up to 30 dB above background levels in the 1–15 Hz frequency range, while vessel noise exhibited PSD peaks between 30 and 60 Hz with increases of up to 5 dB. These observations offered a detailed spatial and temporal resolution for monitoring seismic wave propagation and vessel acoustic noise. The results underscore DAS’s capability as a robust tool for the continuous monitoring of the rich underwater environments in the Gulf of Catania.

Effective Strategies for Automatic Analysis of Acoustic Signals in Long-Term Monitoring - Dídac Diego-Tortosa; Danilo Bonanno; Manuel Bou-Cabo; Letizia S. Di Mauro; Abdelghani Idrissi; Guillermo Lara; Giorgio Riccobene; Simone Sanfilippo; Salvatore Viola (Journal of Marine Science and Engineering, 2025)
Hydrophones used in Passive Acoustic Monitoring generate vast amounts of data, with the storage requirements for raw signals dependent on the sampling frequency, which limits the range of frequencies that can be recorded. Since the installation of these observatories is costly, it is crucial to maximize the utility of high-sampling-rate recordings to expand the range of survey types. However, storing these large datasets for long-term trend analysis presents significant challenges. This paper proposes an approach that reduces the data storage requirements by up to 85% while preserving critical information about Power Spectral Density and Sound Pressure Level. The strategy involves generating these key metrics from spectrograms, enabling both short-term (micro) and long-term (macro) studies. A proposal for efficient data processing is presented, structured in three steps: the first focuses on generating key metrics to replace space-consuming raw signals, the second addresses the treatment of these metrics for long-term studies, and the third outlines the creation of event detectors from the processed metrics. A comprehensive overview of the essential features for analyzing acoustic signals is provided, along with considerations for the future design of marine observatories. The necessary calculations and processes are detailed, demonstrating the potential of these methods to address the current data storage and processing limitations in long-term acoustic monitoring.

Monitoring aerosol optical depth during the Arctic night: Instrument development and first results - Mauro Mazzola; Robert S. Stone; Natalia Kouremeti; Vito Vitale; Julian Gröbner; Kerstin Stebel; Georg H. Hansen; Thomas C. Stone; Christoph Ritter; Simone Pulimeno (Atmospheric Research, 2024)

Comprehensive Analysis of the Aquaporin Genes in Eucalyptus grandis Suggests Potential Targets for Drought Stress Tolerance - Dayana S. Seidel; Paulo H. Claudino; Gabriela Sperotto; Simone N. Wendt; Zachery D. Shomo; Ravi V. Mural; Henrique M. Dias (Tropical Plant Biology, 2024)

Molecular signatures of Haemonchus contortus infection in sheep: A comparative serum proteomic study on susceptible and resistant sheep breeds - Ana Carolina S. Chagas; David M. Ribeiro; Hugo Osório; Ana A.P. Abreu; Cintia H. Okino; Simone C.M. Niciura; Alessandro F.T. Amarante; Hornblenda J.S. Bello; Gláucia R. Melito; Sérgio N. Esteves; André M. Almeida (Veterinary Parasitology, 2024)

Impact of the extreme 2015-16 El Niño climate event on forest and savanna tree species of the Amazonia-Cerrado transition - Nayane C.C.S. Prestes; Beatriz S. Marimon; Paulo S. Morandi; Simone M. Reis; Ben Hur Marimon Junior; Wesley J.A. Cruz; Edmar A. Oliveira; Lucas H. Mariano; Fernando Elias; Denilson M. Santos; Adriane Esquivel-Muelbert; Oliver L. Phillips (Flora, 2024)

Unveiling the antifungal mechanisms of CTP, a new copper(II)-theophylline/1,10-phenanthroline complex, on drug-resistant non-albicans Candida species - Heloisa F. Frota; Pedro F. Barbosa; Carolline M. A. Lorentino; Lorena R. F. Affonso; Lívia S. Ramos; Simone S. C. Oliveira; Lucieri O. P. Souza; Olufunso O. Abosede; Adeniyi S. Ogunlaja; Marta H. Branquinha; André L. S. Santos (BioMetals, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Recent deep-sea nematodes and agglutinated foraminifera select specific grains and bioclasts from their environments: Ecological implications - Sunil K. Das; Raj K. Singh; Mariem Saavedra-Pellitero; Julia Gottschalk; Carlos A. Alvarez Zarikian; Lester Lembke-Jene; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; Chandranath Basak; Anieke Brombacher; et al. (Marine Micropaleontology, 2024)

Circular and sustainable space: Findings from hyperspectral imaging - N. Aversano; G. Bonifazi; I. D'Adamo; R. Palmieri; S. Serranti; A. Simone (Journal of Cleaner Production, 2024)

Late Miocene to Early Pliocene paleoceanographic evolution of the Central South Pacific: A deep-sea benthic foraminiferal perspective - Sunil K. Das; N. Mahanta; B. Sahoo; Raj K. Singh; Carlos A. Alvarez Zarikian; Manish Tiwari; Nishant Vats; Nihal; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Postglacial evolution of the Lake Constance shelf and its relation to a 10-km long chain of submerged Neolithic mounds - Dominic Perler; Simone Benguerel; Hansjörg Brem; Florence Gilliard; Jens Hornung; Thomas Keiser; Urs Leuzinger; Sebastian Schaller; Sönke Szidat; Hendrik Vogel; Martin Wessels; Flavio S. Anselmetti (Journal of Paleolimnology, 2024)
A recent bathymetric survey of Lake Constance revealed ~ 170 mounds composed of loosely deposited rocks aligned in a ~ 10-km long chain along the southern Swiss shoreline in a water depth of 3–5 m. The mounds are 10–30 m in diameter and up to 1.5 m high. Over their entire length of occurrence, the mounds are estimated to be composed of ~ 60 million individual boulders, with a total weight of ~ 78,000 t. A ground penetrating radar (GPR) survey showed that the mounds are not linked to the glacial substrate but were rather deposited artificially on the edge of a prograding shelf composed of Holocene lake sediments. Here, we present the results of a coring campaign with four piston cores along a GPR transect across one of the mounds. The cores recovered the full Holocene sedimentary succession all the way into the basal till that is overlain by lacustrine sediments dating back to ~ 14,400 cal. yrs BP. The four cores are merged into a ~ 12.4-m long composite section reflecting continuous sedimentation from the siliciclastic-dominated Late Glacial to the carbonate-rich Late Holocene. The stratigraphic horizon representing the mound’s construction was radiocarbon-dated to ~ 5600–5300 cal. yrs BP, placing them in the Neolithic period. This age was confirmed by radiocarbon dating of wood samples collected during underwater excavation of the mounds. Geochemical analysis of the Holocene sedimentary succession shows generally high carbonate contents (average of 69%). The interval from 5750 to 4950 cal. yrs BP, a part of the mound period, is characterized by a Holocene minimum in carbonate content (average of 57%) and by larger mean grain sizes. Comparing these values to those from a recent surface-sediment depth transect indicates that this was a period of rather low lake levels, which might have favoured mound construction. Correlations to nearby archaeological sites and to the general West-Central European lake-level record indicates that the mounds likely were built during a short phase of low lake levels during a general trend of climatic cooling followed by a lake-level transgression.

Cytotoxic and molecular evaluation of spilanthol obtained from Acmella oleracea (L.) R. K. Jansen (jambu) in human gastric cancer cells - Mayra Suelen da S. Pinheiro; Daniele A. Moysés; Natasha C. R. Galucio; Willian Oliveira Santos; Jeferson R. Souza Pina; Luana C. Oliveira; Simone Yasue S. Silva; Sebastião da Cruz Silva; Nilton Ferreira Frazão; Patrícia Santana B. Marinho; Andrea L. F. Novais; André S. Khayat; et al. (Natural Product Research, 2024)

Valorization of pyrolytic plastic-derived char for adsorption of wastewater contaminants: a kinetic and thermodynamic investigation - F. Barracco; E. Parisi; G. Pipitone; E. Simone; S. Bensaid; D. Fino (International Journal of Environmental Science and Technology, 2024)
The sustainable management of plastic waste is one of the challenges of our time due to the high percentage of landfilling. One of the strategies is its thermal treatment via pyrolysis, but it is associated with the production of a char, necessitating a proper valorization pathway. In this work, we investigated for the first time the use as adsorbent of a real plastic-derived char obtained as such from a pyrolysis pilot plant. This is a novel approach with respect to literature, where the char is typically obtained as desired product. The adsorbent was characterized via several techniques, and methylene blue was chosen as representative contaminant of wastewater. The inorganic component (80 wt.%) was mainly associated with the presence of rod-like structures, rich in Si, while the organic fraction showed the occurrence of aromatic components. Under the thermodynamic point of view, Langmuir isotherm effectively fitted the experimental data ( R 2 = 0.98), while the kinetic results were well described by a pseudo-second-order law ( R 2 > 0.99). The negative Gibbs free energy highlighted that the adsorption process was spontaneous, and the enthalpy change (∆ H 0 = 7.18 kJ/mol) revealed the endothermic nature of the process, in a range characteristic of physisorption phenomena. Overall, this study highlights that a low-value char, derived from a real plastic waste, can be a promising valuable alternative to expensive adsorbents thanks to its adsorption capacity of 5.8 mg/g without prior activation treatments, hence being a starting point for the development of a holistic approach in plastic waste management.

When is it safe to go home? Post-predation assessment of risk and safety when personal information conflicts with social cues - Brian D. Wisenden; Cat M. Adkins; Seth A. Campbell; Shree Chakraborty; Madelyn E. Cloutier; Alex D. Doebler; Kathryn A. Hanson; Lou Hoff; Molly I. M. Johnson; Philip S. Larson; Claire M. Lukasik; Zoe R. Michaelson; et al. (Behavioral Ecology and Sociobiology, 2024)

Antifungal activity of Lactiplantibacillus plantarum isolated from fruit and vegetables and detection of novel antifungal VOCs from fungal-LAB co-cultures - Nicola De Simone; Lucía López; Carmen S. Ciudad; Angela Scauro; Pasquale Russo; Jorge Rodríguez; Giuseppe Spano; Beatriz Martínez (Food Bioscience, 2024)

Antifungal potential of the new copper(II)-theophylline/1,10-phenanthroline complex against drug-resistant Candida species - Heloisa F. Frota; Carolline M. A. Lorentino; Pedro F. Barbosa; Lívia S. Ramos; Iuri C. Barcellos; Lucas Giovanini; Lucieri O. P. Souza; Simone S. C. Oliveira; Olufunso O. Abosede; Adeniyi S. Ogunlaja; Matheus M. Pereira; Marta H. Branquinha; et al. (BioMetals, 2024)

Assessment of environmental pollution and human health risks of mine tailings in soil: after dam failure of the Córrego do Feijão Mine (in Brumadinho, Brazil) - Andressa Cristhy Buch; Douglas B. Sims; Larissa Magalhães de Ramos; Eduardo Duarte Marques; Simone Ritcher; Mahmood M. S. Abdullah; Emmanoel Vieira Silva-Filho (Environmental Geochemistry and Health, 2024)

Evaluation of the Treatment with Akkermansia muciniphila BAA-835 of Chemotherapy-induced Mucositis in Mice - Ramon O. Souza; Vivian C. Miranda; Mônica F. Quintanilha; Bruno Gallotti; Samantha R. M. Oliveira; Janayne L. Silva; Jacqueline I. Alvarez-Leite; Luís C. L. Jesus; Vasco Azevedo; Kátia D. Vital; Simone O. A. Fernandes; Valbert N. Cardoso; et al. (Probiotics and Antimicrobial Proteins, 2024)

Cardioprotective Effects of Leucine Supplementation against Doxorubicin-Induced Cardiotoxicity - Lucas C. Guimarães; Thiago M. Fidale; Talita C. R. Pereira; Paulo R. Lopes; Marcos D. Ferreira-Junior; Simone R. Deconte; Marcos L. Ferreira-Neto; Willams S. Brito; Rodrigo M. Gomes; Fernanda R. de Souza; Keilah V. N. Cavalcante; Gustavo C. Herrera; et al. (Cardiovascular Toxicology, 2024)

Acoustic recordings, biological observations, and genetic identification of a rare(?) beaked whale in the North Pacific: Mesoplodon carlhubbsi - Lisa T. Ballance; Robert L. Pitman; Jay Barlow; Todd Pusser; Annamaria I. DeAngelis; Craig Hayslip; Ladd Irvine; Debbie Steel; C. Scott Baker; Daniel Gillies; Simone Baumann‐Pickering; Jennifer S. Trickey; et al. (Marine Mammal Science, 2024)
Although Hubbs' beaked whale ( Mesoplodon carlhubbsi ) was previously known from over 60 strandings on both sides of the North Pacific, it had been identified alive in the wild only once, off Oregon in 1994. In September 2021, we conducted a search effort for beaked whales off the coast of Oregon using a towed hydrophone array and a visual search team. Approximately 350 km off the Columbia River mouth, we detected the vocalizations of an unidentified mesoplodont whale; we stopped our vessel and waited in the area until two unidentified juvenile Mesoplodon surfaced and stayed near our vessel for almost 2 hr. During that time, we took numerous photographs and videos, made behavioral observations, and recorded their vocalizations. The DNA sequence from a biopsy sample identified them as M. carlhubbsi . In this paper, we discuss our biological observations, including color patterning and acquired markings, behavioral observations, and describe for the first time the acoustic characteristics of this species. We confirm that M. carlhubbsi is the source of a previously unidentified acoustic signal known as BW37V, and we update what is known about the at‐sea distribution of this species based on previous recordings and observational records.

Geographic distribution of the Cross Seamount beaked whale based on acoustic detections - Jennifer L. K. McCullough; E. Elizabeth Henderson; Jennifer S. Trickey; Jay Barlow; Simone Baumann‐Pickering; Roanne Manzano‐Roth; Gabriela Alongi; Stephen Martin; Selene Fregosi; David K. Mellinger; Holger Klinck; Angela R. Szesciorka; et al. (Marine Mammal Science, 2024)
Beaked whales produce frequency‐modulated echolocation pulses that appear to be species‐specific, allowing passive acoustic monitoring to play a role in understanding spatio‐temporal patterns. The Cross Seamount beaked whale is known only from its unique echolocation signal (BWC) with no confirmed species identification. This beaked whale spans the Pacific Ocean from the Mariana Archipelago to Baja California, Mexico, south to the equator, but only as far north as latitude 29°N. Within these warm waters, 92% of BWC detections occurred at night, 6% during crepuscular periods, and only 2% during daylight hours. Detections of BWC signals on drifting recorders with a vertical hydrophone array at 150 m depth demonstrated that foraging often occurred shallow in the water column (

Groundwater is a hidden global keystone ecosystem - Mattia Saccò; Stefano Mammola; Florian Altermatt; Roman Alther; Rossano Bolpagni; Anton Brancelj; David Brankovits; Cene Fišer; Vasilis Gerovasileiou; Christian Griebler; Simone Guareschi; Grant C. Hose; et al. (Global Change Biology, 2024)
Groundwater is a vital ecosystem of the global water cycle, hosting unique biodiversity and providing essential services to societies. Despite being the largest unfrozen freshwater resource, in a period of depletion by extraction and pollution, groundwater environments have been repeatedly overlooked in global biodiversity conservation agendas. Disregarding the importance of groundwater as an ecosystem ignores its critical role in preserving surface biomes. To foster timely global conservation of groundwater, we propose elevating the concept of keystone species into the realm of ecosystems, claiming groundwater as a keystone ecosystem that influences the integrity of many dependent ecosystems. Our global analysis shows that over half of land surface areas (52.6%) has a medium‐to‐high interaction with groundwater, reaching up to 74.9% when deserts and high mountains are excluded. We postulate that the intrinsic transboundary features of groundwater are critical for shifting perspectives towards more holistic approaches in aquatic ecology and beyond. Furthermore, we propose eight key themes to develop a science‐policy integrated groundwater conservation agenda. Given ecosystems above and below the ground intersect at many levels, considering groundwater as an essential component of planetary health is pivotal to reduce biodiversity loss and buffer against climate change.

EU-compliant wastewater recycled phosphorus: How much national cereal demand can it meet? - Juan Serrano-Gomez; Geneviève S. Metson; Tina-Simone Neset; Jakob Santner; Ludwig Hermann; Matthias Zessner (Journal of Cleaner Production, 2023)

Heavy metals and health risk assessment of Brazilian artisanal cheeses - Luciana S. Rocha; Gustavo Luis P.A. Ramos; Ramon S. Rocha; Bernardo F. Braz; Ricardo E. Santelli; Erick A. Esmerino; Monica Q. Freitas; Eliane T. Mársico; Adriana P.A. Bragotto; Simone L. Quitério; Adriano G. Cruz (Food Research International, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Novel plant-associated genomoviruses from the Brazilian Cerrado biome - Flávia Milene B. Nery; Josiane G. Batista; Felipe Fochat. S. Melo; Simone G. Ribeiro; Leonardo S. Boiteux; Fernando L. Melo; Juliana Gabrielle I. Silva; Luciane de Nazaré A. Reis; Rita C. Pereira-Carvalho (Archives of Virology, 2023)

Overexploitation assessment in an urban karst aquifer: The case of Sete Lagoas (MG), Brazil - Camila S. Schuch; Paulo Galvão; Marília Carvalho de Melo; Simone Pereira (Environmental Research, 2023)

QuOCS: The quantum optimal control suite - Marco Rossignolo; Thomas Reisser; Alastair Marshall; Phila Rembold; Alice Pagano; Philipp J. Vetter; Ressa S. Said; Matthias M. Müller; Felix Motzoi; Tommaso Calarco; Fedor Jelezko; Simone Montangero (Computer Physics Communications, 2023)

Evaluation of a Functional Craft Wheat Beer Fermented with Saccharomyces cerevisiae UFMG A-905 to treat Salmonella Typhimurium infection in mice - Samantha R. M. Oliveira; Lara L. Campos; Maisa N. S. Amaral; Bruno Galotti; Mayra F. Ricci; Katia D. Vital; Ramon O. Souza; Ana Paula T. Uetanabaro; Mateus S. Junqueira; Andreia M. Silva; Simone O. A. Fernandes; Valbert N. Cardoso; et al. (Probiotics and Antimicrobial Proteins, 2023)

Associations of circulating GDF15 with combined cognitive frailty and depression in older adults of the MARK-AGE study - Bastian Kochlik; Catrin Herpich; María Moreno-Villanueva; Susanne Klaus; Ursula Müller-Werdan; Birgit Weinberger; Simone Fiegl; Olivier Toussaint; Florence Debacq-Chainiaux; Christiane Schön; Jürgen Bernhard; Nicolle Breusing; et al. (GeroScience, 2023)
Growth differentiation factor-15 (GDF15) might be involved in the development of cognitive frailty and depression. Therefore, we evaluated cross-sectional associations of plasma GDF15 with combined cognitive-frailty-and-depression in older (i.e. ≥ 55 years) and younger adults of the MARK-AGE study. In the present work, samples and data of MARK-AGE (“European study to establish bioMARKers of human AGEing“) participants ( N = 2736) were analyzed. Cognitive frailty was determined by the global cognitive functioning score (GCF) and depression by the Self-Rating Depression Scale (SDS score). Adults were classified into three groups: (I) neither-cognitive-frailty-nor-depression, (II) either-cognitive-frailty-or-depression or (III) both-cognitive-frailty-and-depression. Cross-sectional associations were determined by unadjusted and by age, BMI, sex, comorbidities and hsCRP-adjusted linear and logistic regression analyses. Cognitive frailty, depression, age and GDF15 were significantly related within the whole study sample. High GDF15 levels were significantly associated with both-cognitive-frailty-and-depression (adjusted β = 0.177 [0.044 – 0.310], p = 0.009), and with low GCF scores and high SDS scores. High GDF15 concentrations and quartiles were significantly associated with higher odds to have both-cognitive-frailty-and-depression (adjusted odds ratio = 2.353 [1.267 – 4.372], p = 0.007; and adjusted odds ratio = 1.414 [1.025 – 1.951], p = 0.035, respectively) independent of age, BMI, sex, comorbidities and hsCRP. These associations remained significant when evaluating older adults. We conclude that plasma GDF15 concentrations are significantly associated with combined cognitive-frailty-and-depression status and, with cognitive frailty and depressive symptoms separately in old as well as young community-dwelling adults.

Association of picky eating around age 4 with dietary intake and weight status in early adulthood: A 14-year follow-up based on the KOALA birth cohort study - Josine Pereboom; Carel Thijs; Simone Eussen; Monique Mommers; Jessica S. Gubbels (Appetite, 2023)

Morpho-anatomical traits and leaf nutrient concentrations vary between plant communities in the Cerrado–Amazonia transition? - Igor Araújo; Marina C. Scalon; Izabel Amorim; Imma Oliveras Menor; Wesley J.A. Cruz; Simone Matias Reis; Priscila F. Simioni; Beatriz S. Marimon (Flora, 2023)

A new firewall in the fight against breast cancer: in-vitro and in-silico studies correlating chemistry to apoptotic activity of Otostegia fruticosa - Somaia. A. Al-Madhagy; Sameh S. Gad; Eman S. Mostafa; Simone Angeloni; Muhammed A Saad; Omar M. Sabry; Giovanni Caprioli; Seham S. El-Hawary (Natural Product Research, 2023)

Acmella oleracea extracts as green pesticides against eight arthropods attacking stored products - Nickolas G. Kavallieratos; Eleonora Spinozzi; Constantin S. Filintas; Erifili P. Nika; Anna Skourti; Anna Maria E. Panariti; Marta Ferrati; Riccardo Petrelli; Massimo Ricciutelli; Simone Angeloni; Ettore Drenaggi; Alessia Sensini; et al. (Environmental Science and Pollution Research, 2023)
Developing sustainable control tools for managing noxious pests attacking stored foodstuffs is a timely research challenge. Acmella oleracea (L.) R. K. Jansen is a crop widely cultivated for its multiple usages on an industrial level. In this study, the extracts prepared with A. oleracea aerial parts were applied on wheat kernels for the management of eight important arthropod pests attacking stored products, i.e., Cryptolestes ferrugineus, Tenebrio molitor, Oryzaephilus surinamensis, Trogoderma granarium, Tribolium castaneum, Tribolium confusum, Alphitobius diaperinus (adults/larvae), and Acarus siro (adults/nymphs). Extraction of A. oleracea was optimized on the base of the yield and content of spilanthol and other N -alkylamides which were analysed by HPLC–DAD-MS. Two concentrations of n -hexane or methanol extracts (500 ppm and 1000 ppm), obtained through Soxhlet extraction, were tested to acquire mortality data on the above-mentioned pests after 4, 8, and 16 h and 1 to 7 days of exposure. Both extracts achieved complete mortality (100.0%) of C. ferrugineus adults. In the case of A. diaperinus adults, mortalities were very low at any concentrations of both extracts. In general, the n -hexane extract was more efficient than methanol extract against almost all species and stages. Considering both extracts, the susceptibility order, from most to least susceptible species/stage, was C. ferrugineus adults > A. diaperinus larvae > C. ferrugineus larvae > T. granarium adults > T. molitor larvae > O. surinamensis adults > O. surinamensis larvae > T. confusum larvae > T. castaneum larvae > A. siro adults > T. molitor adults > A. siro nymphs > T. granarium larvae > T. castaneum adults > T. confusum adults > A. diaperinus adults. Our research provides useful knowledge on the efficacy of N -alkylamides-rich A. oleracea extracts as grain protectants, pointing out the importance of targeting the most susceptible species/ developmental stages.

Concentrations of polycyclic aromatic hydrocarbons (PAHs) in liver samples of green turtles Chelonia mydas stranded in the Potiguar Basin, northeastern Brazil - Silmara Rossi; Daniel Solon Dias de Farias; Aline da Costa Bomfim; Renato S. Carreira; José Henrique Hildebrand Grisi-Filho; Carlos G. Massone; Flávio José de Lima Silva; Simone Almeida Gavilan (Marine Pollution Bulletin, 2023)

The Ability of Ruppia polycarpa to Regenerate from Seed Depends on Seasonal Porewater Salinity Dynamics and Declining Winter Rainfall Could Delay Recruitment - Chanelle L. Webster; Paul S. Lavery; Simone Strydom; Jessica Billinghurst; Kathryn McMahon (Estuaries and Coasts, 2023)
For many plants, regeneration from seed is vital for population recovery. Climate change is modifying the global hydrological cycle and a primary factor controlling germination of marine plants: salinity. How altered salinity regimes, and especially altered porewater salinity regimes, will regulate early life history stages of estuarine seagrasses is poorly understood. Here, we quantified the porewater salinity dynamics in two ephemeral estuaries that are dominated by the cosmopolitan genus Ruppia . Seedbank, germlings (germinated seeds) and seedlings were found in salinities ranging from 5 to 110 over an annual cycle. To understand the germination ecology of the dominant species, Ruppia polycarpa , seeds were exposed to treatments simulating current salinity regimes and those predicted under climate change. Seeds underwent a Dormancy treatment (15, 60, 150) followed by a Germination treatment (10, 20, 80). Generally, early life history stages were positively affected by hypersaline dormancy conditions if the subsequent Germination salinity was ≤ 20. Germination success was significantly higher for seeds transferred to 10 (65%) compared to 20 (49%) whilst no seeds germinated in 80 highlighting the risk of lower germination as estuaries become drier and more hypersaline with declining winter rainfall. However, germlings were found in situ in salinities ≥ 80 suggesting aspects of the salinity dynamics, not captured by our experimental conditions, may broaden tolerances. Dormant seeds were continuously present in situ and seedlings were observed throughout the whole of the growing season. These results are indicative of bet-hedging strategies. Future research should explore the capacity of these strategies to afford resilience to R. polycarpa to salinity variability under climate change.

Coastal landforms and fetch influence shoreline restoration effectiveness - Jason D. Toft; Kerry L. Accola; Simone Des Roches; Julia N. Kobelt; Hannah S. Faulkner; Jason R. Morgan; Bianca S. Perla; Maria Metler; Megan N. Dethier (Frontiers in Marine Science, 2023)
Coastal shorelines are a key interface between terrestrial and aquatic ecosystems and are vital for human livelihood. As a result, shorelines have experienced substantial human modifications worldwide. Shoreline “hardening” – the construction of armor including seawalls, bulkheads, or rip-rap – is a common modification that has substantial negative ecological effects. Currently, restoration involving the removal of armor and replacement with “living” shorelines is becoming an established practice. Still, the ecological response to armor removal is oftentimes unpredictable and site-specific. We hypothesized that the confluence of larger-scale geophysical features might strongly influence ecological restoration outcomes at particular locations. To measure the effectiveness of armor removal in the context of broad-scale geophysical features across the Salish Sea, WA, USA, we studied 26 paired restored and natural reference beaches of the same shoretype (feeder bluff, accretion shoreform, or pocket beach), as well as corresponding fetch, sub-basin, and percent of shoreline sediment drift cell armored. Sites were restored for an average of six years. We gauged restoration effectiveness based on levels of five ecological response variables: beach wrack (percent, depth), logs (count, width), sediments (percent sand), vegetation (percent overhanging, count of fallen trees), and insects (density, taxa richness). We found that armor removal often restored these variables to natural levels, but that restoration response was dependent on geophysical features such as shoretype and fetch. Natural beaches did have higher measurements of overhanging vegetation, fallen trees, and insect taxa richness, as these features likely take time to mature at restored beaches. Feeder bluffs had a higher proportion of surface sand and number of fallen trees than other shoretypes, coinciding with the erosion of bluff material, whereas natural pocket beaches within bordering rocky headlands had higher insect densities. Sites with a large fetch had higher input of deposited wrack and logs, whereas sites with a small fetch had higher input from localized terrestrial sources – fallen trees and eroding sand. By incorporating the effectiveness of restoration with landscape features such as shoretype and fetch, we can more effectively plan for future restoration actions and better predict their outcomes.

Non-thermal emerging processing Technologies: Mitigation of microorganisms and mycotoxins, sensory and nutritional properties maintenance in clean label fruit juices - Simone J.S. Lopes; Anderson S. Sant'Ana; Luísa Freire (Food Research International, 2023)

Effective dispersal and genetic structure of a small mammal in an intensively managed agricultural landscape: is there any barrier to movement? - Marina B. Chiappero; Noelia S. Vera; Lucía V. Sommaro; Ivana Simone; Andrea R. Steinmann; Cristina N. Gardenal; José W. Priotto (Evolutionary Ecology, 2023)

Candida-associated denture stomatitis: clinical, epidemiological, and microbiological features - Jiuyan Qiu; Milena P. Roza; Karolyne G. Colli; Yago R. Dalben; Simone B. Maifrede; Tiago B. Valiatti; Vinicius M. Novo; Rodrigo Cayô; Tânia Regina Grão-Velloso; Sarah S. Gonçalves (Brazilian Journal of Microbiology, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Imaginal retraining reduces craving for high-calorie food - Steffen Moritz; Anja S. Göritz; Simone Kühn; Jürgen Gallinat; Josefine Gehlenborg (Appetite, 2023)

Enhancing the structural diversity between forest patches—A concept and real‐world experiment to study biodiversity, multifunctionality and forest resilience across spatial scales - Jörg Müller; Oliver Mitesser; Marc W. Cadotte; Fons van der Plas; Akira S. Mori; Christian Ammer; Anne Chao; Michael Scherer‐Lorenzen; Petr Baldrian; Claus Bässler; Peter Biedermann; Simone Cesarz; et al. (Global Change Biology, 2023)
Intensification of land use by humans has led to a homogenization of landscapes and decreasing resilience of ecosystems globally due to a loss of biodiversity, including the majority of forests. Biodiversity–ecosystem functioning (BEF) research has provided compelling evidence for a positive effect of biodiversity on ecosystem functions and services at the local (α‐diversity) scale, but we largely lack empirical evidence on how the loss of between‐patch β‐diversity affects biodiversity and multifunctionality at the landscape scale (γ‐diversity). Here, we present a novel concept and experimental framework for elucidating BEF patterns at α‐, β‐, and γ‐scales in real landscapes at a forest management‐relevant scale. We examine this framework using 22 temperate broadleaf production forests, dominated by Fagus sylvatica . In 11 of these forests, we manipulated the structure between forest patches by increasing variation in canopy cover and deadwood. We hypothesized that an increase in landscape heterogeneity would enhance the β‐diversity of different trophic levels, as well as the β‐functionality of various ecosystem functions. We will develop a new statistical framework for BEF studies extending across scales and incorporating biodiversity measures from taxonomic to functional to phylogenetic diversity using Hill numbers. We will further expand the Hill number concept to multifunctionality allowing the decomposition of γ‐multifunctionality into α‐ and β‐components. Combining this analytic framework with our experimental data will allow us to test how an increase in between patch heterogeneity affects biodiversity and multifunctionality across spatial scales and trophic levels to help inform and improve forest resilience under climate change. Such an integrative concept for biodiversity and functionality, including spatial scales and multiple aspects of diversity and multifunctionality as well as physical and environmental structure in forests, will go far beyond the current widely applied approach in forestry to increase resilience of future forests through the manipulation of tree species composition.

Pre-emergent bioherbicide potential of Schinus terebinthifolia Raddi essential oil nanoemulsion for Urochloa brizantha - Simone Y. Fernandes; Débora de Araújo; Montcharles S. Pontes; Jaqueline S. Santos; Claudia A.L. Cardoso; Euclésio Simionatto; Marco A.U. Martines; Débora R. Antunes; Renato Grillo; Gilberto J. Arruda; Etenaldo F. Santiago (Biocatalysis and Agricultural Biotechnology, 2023)

A new arsenal of polyphenols to make Parkinson's disease extinct: HPLC-MS/MS profiling, very interesting MAO-B inhibitory activity and antioxidant activity of Otostegia fruticosa - Somaia A. Al-Madhagy; Sameh S. Gad; Eman S. Mostafa; Simone Angeloni; Muhammed A. Saad; Omar M. Sabry; Giovani Caprioli; Seham S. El-Hawary (Natural Product Research, 2022)

Down a Rabbit Hole: Burrowing Behaviour and Larger Home Ranges are Related to Larger Brains in Leporids - Orlin S. Todorov; Coen Hird; Brian Kraatz; Emma Sherratt; Narelle Hill; Alexandra A. de Sousa; Simone Blomberg; Vera Weisbecker (Journal of Mammalian Evolution, 2022)
Studies on the evolution of brain size variation usually focus on large clades encompassing broad phylogenetic groups. This risks introducing ‘noise’ in the results, often obscuring effects that might be detected in less inclusive clades. Here, we focus on a sample of endocranial volumes (endocasts) of 18 species of rabbits and hares (Lagomorpha: Leporidae), which are a discrete radiation of mammals with a suitably large range of body sizes. Using 60 individuals, we test five popular hypotheses on brain size and olfactory bulb evolution in mammals. We also address the pervasive issue of missing data, using multiple phylogenetic imputations as to conserve the full sample size for all analyses. Our analyses show that home range and burrowing behaviour are the only predictors of leporid brain size variation. Litter size, which is one of the most widely reported constraints on brain size, was unexpectedly not associated with brain size. However, a constraining effect may be masked by a strong association of litter size with temperature seasonality, warranting further study. Lastly, we show that unreasonable estimations of phylogenetic signal (Pagel’s lamba) warrant additional caution when using small sample sizes, such as ours, in comparative studies.

FKBP5 intron 7 methylation is associated with higher anxiety proneness and smaller right thalamus volume in adolescents - Jacqueline S. Womersley; Simone Roeh; Lindi Martin; Fatima Ahmed-Leitao; Susann Sauer; Monika Rex-Haffner; Sian M. J. Hemmings; Elisabeth B. Binder; Soraya Seedat (Brain Structure and Function, 2022)

Variance of coral anti-pathogen defense in response to transplantation between coral- and macroalgal-dominated reefs - Deanna S. Beatty; Cody S. Clements; Jinu Mathew Valayil; Simone Y. Jarvis; Kim B. Ritchie; Frank J. Stewart; Mark E. Hay (Coral Reefs, 2022)

Metastasis suppressor NME1 in exosomes or liposomes conveys motility and migration inhibition in breast cancer model systems - Imran Khan; Brunilde Gril; Ayuko Hoshino; Howard H. Yang; Maxwell P. Lee; Simone Difilippantonio; David C. Lyden; Patricia S. Steeg (Clinical & Experimental Metastasis, 2022)

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Editorial Expression of Concern: “Unfocus” on foc.us: commercial tDCS headset impairs working memory - Laura Steenbergen; Roberta Sellaro; Bernhard Hommel; Ulman Lindenberger; Simone Kühn; Lorenza S. Colzato (Experimental Brain Research, 2022)

Could different aqueous humor and plasma cytokine profiles help differentiate between ocular sarcoidosis and ocular tuberculosis? - L. De Simone; M. Bonacini; R. Aldigeri; F. Alessandrello; V. Mastrofilippo; F. Gozzi; E. Bolletta; C. Adani; A. Zerbini; G. M. Cavallini; L. Fontana; C. Salvarani; et al. (Inflammation Research, 2022)

Correction to: Prevalence and patient‑rated relevance of complexity factors in medication regimens of community dwelling patients with polypharmacy - Viktoria S. Wurmbach; Steffen J. Schmidt; Anette Lampert; Simone Bernard; Andreas D. Meid; Eduard Frick; Michael Metzner; Stefan Wilm; Achim Mortsiefer; Bettina Bücker; Attila Altiner; Lisa Sparenberg; et al. (European Journal of Clinical Pharmacology, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Benefits of permanent adoption of virtual conferences for conservation science - Lauren M. Kuehne; Robert J. Rolls; Kate J. Brandis; Kai Chen; Kevin M. Fraley; Lindsey K. Frost; Susie S. Ho; Erin H. Kunisch; Simone D. Langhans; Carri J. LeRoy; Gregory McDonald; Paul J. McInerney; et al. (Conservation Biology, 2022)

Catchment scale deforestation increases the uniqueness of subtropical stream communities - Fabiana Schneck; Luis M. Bini; Adriano S. Melo; Danielle K. Petsch; Victor S. Saito; Simone Wengrat; Tadeu Siqueira (Oecologia, 2022)

Gene expression of sex steroid metabolizing enzymes and receptors in the skeletal muscle of migrant and resident subspecies of white-crowned sparrow (Zonotrichia leucophrys) - Jesse S. Krause; Trevor Watkins; Angus M. A. Reid; Jeffrey C. Cheah; Jonathan H. Pérez; Valerie R. Bishop; Marilyn Ramenofsky; John C. Wingfield; Simone L. Meddle (Oecologia, 2022)

Prevalence and patient-rated relevance of complexity factors in medication regimens of community-dwelling patients with polypharmacy - Viktoria S. Wurmbach; Steffen J. Schmidt; Anette Lampert; Simone Bernard; Andreas D. Meid; Eduard Frick; Michael Metzner; Stefan Wilm; Achim Mortsiefer; Bettina Bücker; Attila Altiner; Lisa Sparenberg; et al. (European Journal of Clinical Pharmacology, 2022)
Purpose To describe the prevalence of complexity factors in the medication regimens of community-dwelling patients with more than five drugs and to evaluate the relevance of these factors for individual patients. Methods Data were derived from the HIOPP-6 trial, a controlled study conducted in 9 general practices which evaluated an electronic tool to detect and reduce complexity of drug treatment. The prevalence of complexity factors was based on the results of the automated analysis of 139 patients’ medication data. The relevance assessment was based on the patients’ rating of each factor in an interview (48 patients included for analysis). Results A median of 5 (range 0–21) complexity factors per medication regimen were detected and at least one factor was observed in 131 of 139 patients. Almost half of these patients found no complexity factor in their medication regimen relevant. Conclusion In most medication regimens, complexity factors could be identified automatically, yet less than 15% of factors were indeed relevant for patients as judged by themselves. When assessing complexity of medication regimens, one should especially consider factors that are both particularly frequent and often challenging for patients, such as use of inhalers or tablet splitting. Trial registration The HIOPP-6 trial was registered retrospectively on May 17, 2021, in the German Clinical Trials register under DRKS-ID DRKS00025257.

Antarctic Strain of Rhodotorula mucilaginosa UFMGCB 18,377 Attenuates Mucositis Induced by 5-Fluorouracil in Mice - Joana O. P. A. Coutinho; Mônica F. Quintanilha; Marina R. A. Campos; Enio Ferreira; Graciéle C. A. de Menezes; Luiz H. Rosa; Carlos A. Rosa; Katia D. Vital; Simone O. A. Fernandes; Valbert N. Cardoso; Jacques R. Nicoli; Fabiana C. P. Tiago; et al. (Probiotics and Antimicrobial Proteins, 2022)

Local drivers of heterogeneity in a tropical forest: epiphytic tank bromeliads affect the availability of soil resources and conditions and indirectly affect the structure of seedling communities - Tháles A. Pereira; Simone A. Vieira; Rafael S. Oliveira; Pablo A. P. Antiqueira; Gustavo H. Migliorini; Gustavo Q. Romero (Oecologia, 2022)

Neutral Sphingomyelinase 2 Mediates Oxidative Stress Effects on Astrocyte Senescence and Synaptic Plasticity Transcripts - Zhihui Zhu; Zainuddin Quadri; Simone M. Crivelli; Ahmed Elsherbini; Liping Zhang; Priyanka Tripathi; Haiyan Qin; Emily Roush; Stefka D. Spassieva; Mariana Nikolova-Karakashian; Timothy S. McClintock; Erhard Bieberich (Molecular Neurobiology, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

Sucrose intake by rats affected by both intraperitoneal oxytocin administration and time of day - Simone Rehn; Joel S. Raymond; Robert A. Boakes; Michael T. Bowen (Psychopharmacology, 2022)

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

ATLANTIC POLLINATION: a data set of flowers and interaction with nectar‐feeding vertebrates from the Atlantic Forest - Joice Iamara‐Nogueira; Natália Targhetta; Gina Allain; Adriano Gambarini; Alessandra R. Pinto; Ana Maria Rui; Andréa C. Araújo; Ariadna Lopes; Brenda Pereira‐Silva; Bruna Bertagni de Camargo; Caio Graco Machado; Caio Missagia; et al. (Ecology, 2022)
Flowering plant species and their nectar‐feeding vertebrates exemplify some of the most remarkable biotic interactions in the Neotropics. In the Brazilian Atlantic Forest, several species of birds (especially hummingbirds), bats, and non‐flying mammals, as well as one lizard feed on nectar, often act as pollinators and contribute to seed output of flowering plants. We present a dataset containing information on flowering plants visited by nectar‐feeding vertebrates and sampled at 166 localities in the Brazilian Atlantic Forest. This dataset provides information on 1902 unique interactions among 515 species of flowering plants and 129 species of potential vertebrate pollinators and the patterns of species diversity across latitudes. All plant–vertebrate interactions compiled were recorded through direct observations of visits, and no inferences of pollinators based on floral syndromes were included. We also provide information on the most common plant traits used to understand the interactions between flowers and nectar‐feeding vertebrates: plant growth form, corolla length, rate of nectar production per hour in bagged flowers, nectar concentration, flower color and shape, time of anthesis, presence or absence of perceptible fragrance by human, and flowering phenology as well as the plant’s threat status by International Union for Conservation of Nature (IUCN) classification. For the vertebrates, status of threat by IUCN classification, body mass, bill or rostrum size are provided. Information on the frequency of visits and pollen deposition on the vertebrate’s body is provided from the original source when available. The highest number of unique interactions is recorded for birds (1771) followed by bats (110). For plants, Bromeliaceae contains the highest number of unique interactions (606), followed by Fabaceae (242) and Gesneriaceae (104). It is evident that there was geographical bias of the studies throughout the southeast of the Brazilian Atlantic Forest and that most effort was directed to flower–hummingbird interactions. However, it reflects a worldwide tendency of more plants interacting with birds compared with other vertebrate species. The lack of similar protocols among studies to collect basic data limits the comparisons among areas and generalizations. Nevertheless, this dataset represents a notable effort to organize and highlight the importance of vertebrate pollinators in this hotspot of biodiversity on Earth and represents the data currently available. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or scientific events.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Evaluation of pharmacogenomics and hepatic nuclear imaging–related covariates by population pharmacokinetic models of irinotecan and its metabolites - Zheng Liu; Jennifer H. Martin; Winston Liauw; Sue-Anne McLachlan; Emma Link; Anetta Matera; Michael Thompson; Michael Jefford; Rod J. Hicks; Carleen Cullinane; Athena Hatzimihalis; Ian Campbell; et al. (European Journal of Clinical Pharmacology, 2022)

Long-Term Patterns of Noise From Underwater Explosions and Their Relation to Fisheries in Southern California - Anna Krumpel; Ally Rice; Kaitlin E. Frasier; Fairlie Reese; Jennifer S. Trickey; Anne E. Simonis; John P. Ryan; Sean M. Wiggins; Annette Denzinger; Hans-Ulrich Schnitzler; Simone Baumann-Pickering (Frontiers in Marine Science, 2021)
Acoustic deterrents can reduce marine mammal interactions with fisheries and aquacultures, but they contribute to an increasing level of underwater noise. In Southern California, commercially produced explosive deterrents, commonly known as “seal bombs,” are used to protect fishing gear and catch from pinniped predation, which can cause extensive economic losses for the fishing community. Passive acoustic monitoring data collected between 2005 and 2016 at multiple sites within the Southern California Bight and near Monterey Bay revealed high numbers of these small-charge underwater explosions, long-term, spatio-temporal patterns in their occurrence, and their relation to different commercial purse-seine fishing sectors. The vast majority of explosions occurred at nighttime and at many nearshore sites high explosion counts were detected, up to 2,800/day. Received sound exposure levels of up to 189 dB re 1 μPa 2 -s indicate the potential for negative effects on marine life, especially in combination with the persistence of recurring explosions during periods of peak occurrence. Due to the highly significant correlation and similar spatio-temporal patterns of market squid landings and explosion occurrence at many sites, we conclude that the majority of the recorded explosions come from seal bombs being used by the California market squid purse-seine fishery. Additionally, seal bomb use declined over the years of the study, potentially due to a combination of reduced availability of market squid driven by warm water events in California and regulation enforcement. This study is the first to provide results on the distribution and origin of underwater explosions off Southern California, but there is a substantial need for further research on seal bomb use in more recent years and their effects on marine life, as well as for establishing environmental regulations on their use as a deterrent.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Characterizing the Long-Term, Wide-Band and Deep-Water Soundscape Off Hawai’i - Karlina Merkens; Simone Baumann-Pickering; Morgan A. Ziegenhorn; Jennifer S. Trickey; Ann N. Allen; Erin M. Oleson (Frontiers in Marine Science, 2021)
Many animals use sound for communication, navigation, and foraging, particularly in deep water or at night when light is limited, so describing the soundscape is essential for understanding, protecting, and managing these species and their environments. The nearshore deep-water acoustic environment off the coast of Kona, Hawai’i, is not well documented but is expected to be strongly influenced by anthropogenic activities such as fishing, tourism, and other vessel activity. To characterize the deep-water soundscape in this area we used High-frequency Acoustic Recording Packages (HARPs) to record acoustic data year-round at a 200 or 320 kHz sampling rate. We analyzed data spanning more than 10 years (2007-2018) by producing measurements of frequency-specific energy and using a suite of detectors and classifiers for general and specific sound sources. This provided a time series for sounds coming from biological, anthropogenic and physical sources. The soundscape in this location is dominated by signals generated by humans and odontocete cetaceans (mostly delphinids), generally alternating on a diel cycle. During daylight hours the dominant sound sources are vessels and echosounders, with strong signals ranging from 10 Hz to 80 kHz and above, while during the night the clicks from odontocetes dominate the soundscape in mid-to-high frequencies, generally between 10 and 90 kHz. Winter-resident humpback whales are present seasonally and produce calls in lower frequencies (200-2,000 Hz). Overall, seasonal variability is relatively subtle, which is unsurprising given the tropical latitude and deep-water environment. These results, and particularly the inclusion of sounds from frequencies above 2 kHz, represent the first long-term analysis of a marine soundscape in the North Pacific, and the first assessment of the intense, daily presence of manmade noise at this site. The decadal time series allows us to characterize the dynamic nature of this location, and to begin to identify changes in the soundscape over time. This type of analysis facilitates protection of natural resources and effective management of human activities in an ecologically important area.

On the Use of Interferometric Synthetic Aperture Radar Data for Monitoring and Forecasting Natural Hazards - Mara S. Bernardi; Pasquale C. Africa; Carlo de Falco; Luca Formaggia; Alessandra Menafoglio; Simone Vantini (Mathematical Geosciences, 2021)
Recent advances in satellite technologies, statistical and mathematical models, and computational resources have paved the way for operational use of satellite data in monitoring and forecasting natural hazards. We present a review of the use of satellite data for Earth observation in the context of geohazards preventive monitoring and disaster evaluation and assessment. We describe the techniques exploited to extract ground displacement information from satellite radar sensor images and the applicability of such data to the study of natural hazards such as landslides, earthquakes, volcanic activity, and ground subsidence. In this context, statistical techniques, ranging from time series analysis to spatial statistics, as well as continuum or discrete physics-based models, adopting deterministic or stochastic approaches, are irreplaceable tools for modeling and simulating natural hazards scenarios from a mathematical perspective. In addition to this, the huge amount of data collected nowadays and the complexity of the models and methods needed for an effective analysis set new computational challenges. The synergy among statistical methods, mathematical models, and optimized software, enriched with the assimilation of satellite data, is essential for building predictive and timely monitoring models for risk analysis.

Human astrovirus types 1, 4 and 5 circulating among children with acute gastroenteritis in a rural Brazilian state, 2010-2016 - Adriana Luchs; Kaelan Tardy; Roozbeh Tahmasebi; Simone Guadagnucci Morillo; Flavio Augusto de Pádua Milagres; Vanessa dos Santos Morais; Rafael Brustulin; Maria da Aparecida Rodrigues Teles; Lais Sampaio de Azevedo; Ellen Viana de Souza; Roberta Salzone Medeiros; Yasmin França Viana Pires de Souza; et al. (Archives of Virology, 2021)

Do-not-intubate status and COVID-19 mortality in patients admitted to Dutch non-ICU wards - Tjeerd van der Veer; Simone van der Sar-van der Brugge; Marthe S. Paats; Els van Nood; Ingrid C. de Backer; Joachim G. J. V. Aerts; Menno M. van der Eerden (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
Mortality from COVID-19 has been particularly high in elderly patients on mechanical ventilation. Treatment outcomes for patients with do-not-intubate (DNI) status are unknown. One hundred patients admitted to the non-ICU ward during the “first wave” were retrospectively analyzed. Mortality rate was 49% in patients with a DNI order. This subgroup was characterized by significantly higher age, more comorbidity, and care dependency. Mortality among DNI patients was three times higher than other patients, but not higher than some of the published mortality rates for elderly mechanically ventilated patients. Advanced care planning is essential in COVID-19 to assist patient autonomy and prevent non-beneficial medical interventions.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Cetacean occurrence offshore of Washington from long-term passive acoustic monitoring - Ally Rice; Amanda J. Debich; Ana Širović; Erin M. Oleson; Jennifer S. Trickey; Leah M. Varga; Sean M. Wiggins; John A. Hildebrand; Simone Baumann-Pickering (Marine Biology, 2021)
A variety of cetacean species inhabit the productive waters offshore of Washington State, USA. Although the general presence of many of these species has been documented in this region, our understanding of fine-scale habitat use is limited. Here, passive acoustic monitoring was used to investigate the spatial and temporal distributions of ten cetacean species at three locations offshore of Washington. Between 2004 and 2013, a total of 2845 days of recordings were collected from sites on the continental shelf and slope, and in a submarine canyon. Acoustic presence was higher for all species at sites farther offshore. Detections were highest during the fall and winter for blue ( Balaenoptera musculus ), fin ( B. physalus ), and humpback whales ( Megaptera novaeangliae ), likely related to reproductive behavior, while minke whales ( B. acutorostrata ) were only detected on two days. Odontocetes showed temporal separation, with sperm whale ( Physeter macrocephalus ) detections highest in spring, Risso’s ( Grampus griseus ) and Pacific white-sided dolphins ( Lagenorhynchus obliquidens ) highest in summer, and Stejneger’s beaked whales ( Mesoplodon stejnegeri ), Cuvier’s beaked whales ( Ziphius cavirostris ), and the BW37V signal type highest in winter or spring. There was interannual variation in detections for most mysticete species, which may be linked to oceanographic conditions: blue and fin whale detections increased during 2007 and 2008, and fin and humpback whale detections increased in 2011. These results inform our understanding of cetacean behavior and habitat use in this region and may aid in the development of conservation strategies suited to the dynamic conditions that drive cetacean distribution.

Cetacean occurrence in the Gulf of Alaska from long-term passive acoustic monitoring - Ally Rice; Ana Širović; Jennifer S. Trickey; Amanda J. Debich; Rachel S. Gottlieb; Sean M. Wiggins; John A. Hildebrand; Simone Baumann-Pickering (Marine Biology, 2021)
The Gulf of Alaska is an important habitat for a diverse array of marine mammals, many of which were severely depleted by historical whaling. To study current cetacean distributions in this region, passive acoustic monitoring was used to detect species-specific call types between 2011 and 2015 at five locations spanning the continental shelf, slope, and offshore seamounts. Spatial and temporal detection patterns were examined for nine species to compare differences in behavior and habitat use. Mysticetes showed seasonal increases in calling that indicated possible behavioral shifts between feeding and breeding in blue ( Balaenoptera musculus ), fin ( B. physalus ), and humpback ( Megaptera novaeangliae ) whales, and matched known migration timing of gray whales ( Eschrichtius robustus ). Interannual changes in blue and fin whale calling may relate to the marine heat wave that began in 2013 and lasted through the end of the monitoring period. Odontocete detections revealed unique spatial distributions, with killer whales ( Orcinus orca ) most common on the continental shelf and sperm whales ( Physeter macrocephalus ) most common on the continental slope, where detections occurred year-round. Beaked whales showed both spatial and temporal separation: Baird’s beaked whale ( Berardius bairdii ) detections were highest at Quinn Seamount in the spring, Cuvier’s ( Ziphius cavirostris ) at Pratt Seamount in winter, and Stejneger’s ( Mesoplodon stejnegeri ) on the continental slope in the fall. The year-round presence of many species highlights the ecological importance of the Gulf of Alaska and the spatiotemporal information reported here should inform future conservation efforts.

Main bacterial species causing clinical disease in ornamental freshwater fish in Brazil - Pedro H. M. Cardoso; Luisa Z. Moreno; Carolina H. de Oliveira; Vasco T. M. Gomes; Ana Paula S. Silva; Mikaela R. F. Barbosa; Maria Inês Z. Sato; Simone C. Balian; Andrea M. Moreno (Folia Microbiologica, 2021)

Muricauda brasiliensis sp. nov., isolated from a mat-forming cyanobacterial culture - Carla Simone Vizzotto; Julianna Peixoto; Stefan Joshua Green; Fabyano Alvares C. Lopes; Marcelo Henrique S. Ramada; Osmindo R. Pires Júnior; Otávio Henrique B. Pinto; Marcos Rogério Tótola; Fabiano Lopes Thompson; Ricardo Henrique Krüger (Brazilian Journal of Microbiology, 2021)

Evaluation of climate simulations produced with the Brazilian global atmospheric model version 1.2 - Caio A. S. Coelho; Dayana C. de Souza; Paulo Y. Kubota; Simone M. S. Costa; Layrson Menezes; Bruno S. Guimarães; Silvio N. Figueroa; José P. Bonatti; Iracema F. A. Cavalcanti; Gilvan Sampaio; Nicholas P. Klingaman; Jessica C. A. Baker (Climate Dynamics, 2021)

Brain tissue transcriptomic analysis of SIV-infected macaques identifies several altered metabolic pathways linked to neuropathogenesis and poly (ADP-ribose) polymerases (PARPs) as potential therapeutic targets - Carla Mavian; Andrea S. Ramirez-Mata; James Jarad Dollar; David J. Nolan; Melanie Cash; Kevin White; Shannan N. Rich; Brittany Rife Magalis; Simone Marini; Mattia C. F. Prosperi; David Moraga Amador; Alberto Riva; et al. (Journal of NeuroVirology, 2021)
Despite improvements in antiretroviral therapy, human immunodeficiency virus type 1 (HIV-1)-associated neurocognitive disorders (HAND) remain prevalent in subjects undergoing therapy. HAND significantly affects individuals’ quality of life, as well as adherence to therapy, and, despite the increasing understanding of neuropathogenesis, no definitive diagnostic or prognostic marker has been identified. We investigated transcriptomic profiles in frontal cortex tissues of Simian immunodeficiency virus (SIV)-infected Rhesus macaques sacrificed at different stages of infection. Gene expression was compared among SIV-infected animals ( n = 11), with or without CD8+ lymphocyte depletion, based on detectable ( n = 6) or non-detectable ( n = 5) presence of the virus in frontal cortex tissues. Significant enrichment in activation of monocyte and macrophage cellular pathways was found in animals with detectable brain infection, independently from CD8+ lymphocyte depletion. In addition, transcripts of four poly (ADP-ribose) polymerases (PARPs) were up-regulated in the frontal cortex, which was confirmed by real-time polymerase chain reaction. Our results shed light on involvement of PARPs in SIV infection of the brain and their role in SIV-associated neurodegenerative processes. Inhibition of PARPs may provide an effective novel therapeutic target for HIV-related neuropathology.

Diverse genomoviruses representing twenty-nine species identified associated with plants - Rafaela S. Fontenele; Philippe Roumagnac; Cécile Richet; Simona Kraberger; Daisy Stainton; Maketalena Aleamotu‘a; Denis Filloux; Pauline Bernardo; Gordon W. Harkins; James McCarthy; Lachlan S. Charles; Natalia S. Lamas; et al. (Archives of Virology, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Rare earth elements (REE) in biology and medicine - P. Ascenzi; M. Bettinelli; A. Boffi; M. Botta; G. De Simone; C. Luchinat; E. Marengo; H. Mei; S. Aime (Rendiconti Lincei. Scienze Fisiche e Naturali, 2020)
This survey reports on topics that were presented at the workshop on “Challenges with Rare Earth Elements. The Periodic Table at work for new Science & Technology” hold at the Academia dei Lincei in November 2019. The herein reported materials refer to presentations dealing with studies and applications of rare earth elements (REE) in several areas of Biology and Medicine. All together they show the tremendous impact REE have in relevant fields of living systems and highlight, on one hand, the still existing knowledge gap for an in-depth understanding of their function in natural systems as well as the very important role they already have in providing innovative scientific and technological solutions in a number of bio-medical areas and in fields related to the assessment of the origin of food and on their manufacturing processes. On the basis of the to-date achievements one expects that new initiatives will bring, in a not too far future, to a dramatic increase of our understanding of the REE involvement in living organisms as well as a ramp-up in the exploitation of the peculiar properties of REE for the design of novel applications in diagnostic procedures and in the set-up of powerful medical devices. This scenario calls the governmental authorities for new responsibilities to guarantee a continuous availability of REE to industry and research labs together with providing support to activities devoted to their recovery/recycling.

The National Autism Database of Israel: a Resource for Studying Autism Risk Factors, Biomarkers, Outcome Measures, and Treatment Efficacy - Ilan Dinstein; Ayelet Arazi; Hava M. Golan; Judah Koller; Evan Elliott; Illana Gozes; Cory Shulman; Sagiv Shifman; Raanan Raz; Nadav Davidovitch; Tali Gev; Adi Aran; et al. (Journal of Molecular Neuroscience, 2020)

The composition of the bacterial community in the foam produced by Mahanarva fimbriolata is distinct from those at gut and soil - Mateus Tonelli; Simone Raposo Cotta; Alessandra Rigotto; Armando Cavalcante F. Dias; Fernando Dini Andreote; José Maurício S. Bento (Brazilian Journal of Microbiology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Towards a rigorous species delimitation framework for scleractinian corals based on RAD sequencing: the case study of Leptastrea from the Indo-Pacific - Roberto Arrigoni; Michael L. Berumen; Kiruthiga G. Mariappan; Pieter S. A. Beck; Ann Marie Hulver; Simone Montano; Michel Pichon; Giovanni Strona; Tullia Isotta Terraneo; Francesca Benzoni (Coral Reefs, 2020)

Origin and history of Phoxinus (Cyprinidae) introductions in the Douro Basin (Iberian Peninsula): an update inferred from genetic data - Aina Garcia-Raventós; Filipa M. S. Martins; Amilcar Teixeira; Ronaldo Sousa; Elsa Froufe; Simone Varandas; Manuel Lopes-Lima; Pedro Beja; Ana Filipa Filipe (Biological Invasions, 2020)

Individual factors increasing complexity of drug treatment—a narrative review - Steffen J. Schmidt; Viktoria S. Wurmbach; Anette Lampert; Simone Bernard; Walter E. Haefeli; Hanna M. Seidling; Petra A. Thürmann (European Journal of Clinical Pharmacology, 2020)
Purpose Complexity of drug treatment is known to be a risk factor for administration errors and nonadherence promoting higher healthcare costs, hospital admissions and increased mortality. Number of drugs and dose frequency are parameters often used to assess complexity related to the medication regimen. However, factors resulting from complex processes of care or arising from patient characteristics are only sporadically analyzed. Hence, the objective of this review is to give a comprehensive overview of relevant, patient-centered factors influencing complexity of drug treatment. Methods A purposeful literature search was performed in MEDLINE to identify potential complexity factors relating to the prescribed drug (i.e. dosage forms or other product characteristics), the specific medication regimen (i.e. dosage schemes or additional instructions), specific patient characteristics and process characteristics. Factors were included if they were associated to administration errors, nonadherence and related adverse drug events detected in community dwelling adult patients. Results Ninety-one influencing factors were identified: fourteen in “dosage forms”, five in “product characteristics”, twelve in “dosage schemes”, nine in “additional instructions”, thirty-one in “patient characteristics” and twenty in “process characteristics”. Conclusions Although the findings are limited by the non-systematic search process and the heterogeneous results, the search shows the influence of many factors on the complexity of drug treatment. However, to evaluate their relevance for individual patients, prospective studies are necessary.

Evaluation of the anti-apoptotic activity of bovine alphaherpesvirus type 5 US3 protein kinase in insect cells using a recombinant baculovirus - Alice M. Silva; Fabrício S. Morgado; Leonardo A. Silva; José R. J. Borges; Simone Perecmanis; Daniel M. P. Ardisson-Araújo; Bergmann M. Ribeiro; Fabrício S. Campos (Brazilian Journal of Microbiology, 2020)

Efficacy of a native isolate of the entomopathogenic fungus Metarhizium anisopliae against larval tick outbreaks under semifield conditions - Emily Mesquita; Allan F. Marciano; Amanda R. C. Corval; Jéssica Fiorotti; Thaís A. Corrêa; Simone Quinelato; Vânia R. E. P. Bittencourt; Patrícia S. Golo (BioControl, 2020)

Rainfall manipulation experiments as simulated by terrestrial biosphere models: Where do we stand? - Athanasios Paschalis; Simone Fatichi; Jakob Zscheischler; Philippe Ciais; Michael Bahn; Lena Boysen; Jinfeng Chang; Martin De Kauwe; Marc Estiarte; Daniel Goll; Paul J. Hanson; Anna B. Harper; et al. (Global Change Biology, 2020)
Changes in rainfall amounts and patterns have been observed and are expected to continue in the near future with potentially significant ecological and societal consequences. Modelling vegetation responses to changes in rainfall is thus crucial to project water and carbon cycles in the future. In this study, we present the results of a new model‐data intercomparison project, where we tested the ability of 10 terrestrial biosphere models to reproduce the observed sensitivity of ecosystem productivity to rainfall changes at 10 sites across the globe, in nine of which, rainfall exclusion and/or irrigation experiments had been performed. The key results are as follows: (a) Inter‐model variation is generally large and model agreement varies with timescales. In severely water‐limited sites, models only agree on the interannual variability of evapotranspiration and to a smaller extent on gross primary productivity. In more mesic sites, model agreement for both water and carbon fluxes is typically higher on fine (daily–monthly) timescales and reduces on longer (seasonal–annual) scales. (b) Models on average overestimate the relationship between ecosystem productivity and mean rainfall amounts across sites (in space) and have a low capacity in reproducing the temporal (interannual) sensitivity of vegetation productivity to annual rainfall at a given site, even though observation uncertainty is comparable to inter‐model variability. (c) Most models reproduced the sign of the observed patterns in productivity changes in rainfall manipulation experiments but had a low capacity in reproducing the observed magnitude of productivity changes. Models better reproduced the observed productivity responses due to rainfall exclusion than addition. (d) All models attribute ecosystem productivity changes to the intensity of vegetation stress and peak leaf area, whereas the impact of the change in growing season length is negligible. The relative contribution of the peak leaf area and vegetation stress intensity was highly variable among models.

Tree diversity and above-ground biomass in the South America Cerrado biome and their conservation implications - Paulo S. Morandi; Beatriz Schwantes Marimon; Ben Hur Marimon-Junior; James A. Ratter; Ted R. Feldpausch; Guarino Rinaldi Colli; Cássia Beatriz Rodrigues Munhoz; Manoel Cláudio da Silva Júnior; Edson de Souza Lima; Ricardo Flores Haidar; Luzmila Arroyo; Alejandro Araujo Murakami; et al. (Biodiversity and Conservation, 2020)

Keap1/Nrf2/HO-1 signaling pathway contributes to p-chlorodiphenyl diselenide antidepressant-like action in diabetic mice - Vanessa A. Zborowski; Suélen O. Heck; Marina Vencato; Simone Pinton; Luiza S. Marques; Cristina W. Nogueira (Psychopharmacology, 2020)

Cumulative biomass curves describe past and present conditions of Large Marine Ecosystems - Fabio Pranovi; Simone Libralato; Matteo Zucchetta; Marco Anelli Monti; Jason S. Link (Global Change Biology, 2020)
Implementing the Ecosystem Approach in marine ecosystems is moving from preliminary steps—dedicated to defining the optimal features for indicators and developing efficient indicator frameworks—towards an operational phase where multisector marine management decisions are executed using this information. Within this operational context, emergent ecosystem properties are becoming quite promising as they have been demonstrated to be globally widespread and repeatable, and to be quite effective in detecting significant state variations of complex systems. Biomass accumulation across TLs (CumB‐TL) combines two important emergent properties of an ecosystem (energy flow, in terms of transfer efficiency, and storage, expressed as biomass), both amenable to detecting rapid ecosystem change. However, for further application, it is crucial to understand which types of drivers an indicator is sensitive to and how robust it is in relation to modifications of the external conditions and/or the system state. Here we address some outstanding questions of these CumB‐TL curves related to their sensitivity to various drivers by carrying out a global scale assessment (using data from 62 LMEs) over six decades (1950–2010). We confirm the consistency of the S‐pattern across all the LMEs, independent from latitude, ecosystem, environmental conditions, and stress level. The dynamics of the curve shape showed a tendency to stretch (i.e. decrease of steepness), in the presence of external disturbance and conversely to increase in steepness and shift towards higher TL in the case of recovery from stressed conditions. Our results suggest the presence of three main types of ecosystem dynamics, those showing an almost continuous increase in ecological state over time, those showing a continuous decrease in ecological state over time, and finally those showing a mixed behaviour flipping between recovering and degrading phases. These robust patterns suggest that the CumB‐TL curve approach has some useful properties for use in further advancing the implementation of the Ecosystem Approach, allowing us to detect the state of a given marine ecosystem based on the dynamics of its curve shape, by using readily available time series data. The value of being able to identify conditions that might require management actions is quite high and, in many respects, represents the main objective in the context of an Ecosystem Approach, with large applications for detecting and responding to global changes in marine ecosystems.

Inactivation of the dorsolateral periaqueductal gray matter impairs the promoting influence of stress on fear memory during retrieval - Marcelo Giachero; Eloisa Pavesi; Gastón Calfa; Simone C. Motta; Newton S. Canteras; Víctor A. Molina; Antonio P. Carobrez (Brain Structure and Function, 2019)

Straw Removal Effects on Soil Water Dynamics, Soil Temperature, and Sugarcane Yield in South-Central Brazil - Simone Toni Ruiz Corrêa; Leandro Carneiro Barbosa; Lauren Maine S. Menandro; Fábio Vale Scarpare; Klaus Reichardt; Luana Oliveira de Moraes; Thayse Aparecida Dourado Hernandes; Henrique Coutinho Junqueira Franco; João Luis Nunes Carvalho (BioEnergy Research, 2019)

Global mismatches in aboveground and belowground biodiversity - Erin K. Cameron; Inês S. Martins; Patrick Lavelle; Jérôme Mathieu; Leho Tedersoo; Mohammad Bahram; Felix Gottschall; Carlos A. Guerra; Jes Hines; Guillaume Patoine; Julia Siebert; Marten Winter; et al. (Conservation Biology, 2019)
Human activities are accelerating global biodiversity change and have resulted in severely threatened ecosystem services. A large proportion of terrestrial biodiversity is harbored by soil, but soil biodiversity has been omitted from many global biodiversity assessments and conservation actions, and understanding of global patterns of soil biodiversity remains limited. In particular, the extent to which hotspots and coldspots of aboveground and soil biodiversity overlap is not clear. We examined global patterns of these overlaps by mapping indices of aboveground (mammals, birds, amphibians, vascular plants) and soil (bacteria, fungi, macrofauna) biodiversity that we created using previously published data on species richness. Areas of mismatch between aboveground and soil biodiversity covered 27% of Earth's terrestrial surface. The temperate broadleaf and mixed forests biome had the highest proportion of grid cells with high aboveground biodiversity but low soil biodiversity, whereas the boreal and tundra biomes had intermediate soil biodiversity but low aboveground biodiversity. While more data on soil biodiversity are needed, both to cover geographic gaps and to include additional taxa, our results suggest that protecting aboveground biodiversity may not sufficiently reduce threats to soil biodiversity. Given the functional importance of soil biodiversity and the role of soils in human well‐being, soil biodiversity should be considered further in policy agendas and conservation actions by adapting management practices to sustain soil biodiversity and considering soil biodiversity when designing protected areas.

Responses of coppiced Eucalyptus to macro- and micronutrient application - José Henrique T. Rocha; Andréa V. A. Wenzel; Eduardo A. S. C. Melo; Ângela Simone Freitag Lima; Rodrigo Eiji Hakamada; Alexandre de Vicente Ferraz; José Carlos Arthur Junior; José Leonardo de Moraes Gonçalves; Gabriela Moreira; Antônio Natal Gonçalves (New Forests, 2019)

7-Chloro-4-(Phenylselanyl) Quinoline with Memory Enhancer Action in Aging Rats: Modulation of Neuroplasticity, Acetylcholinesterase Activity, and Cholesterol Levels - Anelise Barth; Ane G. Vogt; Angélica S. dos Reis; Mikaela P. Pinz; Roberta Krüger; William B. Domingues; Diego Alves; Vinicius F. Campos; Simone Pinton; Natália Paroul; Ethel A. Wilhelm; Cristiane Luchese (Molecular Neurobiology, 2019)

Optimum salinity for Nile tilapia (Oreochromis niloticus) growth and mRNA transcripts of ion-regulation, inflammatory, stress- and immune-related genes - Ahmed A. A. El-Leithy; Shaaban A. Hemeda; Walaa S. H. Abd El Naby; Abeer F. El Nahas; Seham A. H. Hassan; Simone T. Awad; Safaa I. El-Deeb; Zeinab A. Helmy (Fish Physiology and Biochemistry, 2019)

A Systematic Review of How Multiple Stressors From an Extreme Event Drove Ecosystem-Wide Loss of Resilience in an Iconic Seagrass Community - Gary A. Kendrick; Robert J. Nowicki; Ylva S. Olsen; Simone Strydom; Matthew W. Fraser; Elizabeth A. Sinclair; John Statton; Renae K. Hovey; Jordan A. Thomson; Derek A. Burkholder; Kathryn M. McMahon; Kieryn Kilminster; et al. (Frontiers in Marine Science, 2019)

Assessing Seasonality and Density From Passive Acoustic Monitoring of Signals Presumed to be From Pygmy and Dwarf Sperm Whales in the Gulf of Mexico - John A. Hildebrand; Kaitlin E. Frasier; Simone Baumann-Pickering; Sean M. Wiggins; Karlina P. Merkens; Lance P. Garrison; Melissa S. Soldevilla; Mark A. McDonald (Frontiers in Marine Science, 2019)

Natural products from Pluchea sagittalis act as inhibitors of photosynthesis in vitro - Ana C. Carvalho; João C. S. Lira; Thaís M. Pereira; Sebastião C. Silva; Simone Y. Simote-Silva; Fernando K. D. Oliveira; Beatriz King-Diaz; Blas Lotina-Hennsen; Thiago A. M. Veiga (Natural Product Research, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Synthesis and evaluation of cadiolide analogues as inhibitors of bacterial biofilm formation - Simone Z. Mairink; Luiz C. A. Barbosa; John Boukouvalas; Silvia H. S. P. Pedroso; Simone G. Santos; Paula P. Magalhães; Luiz M. Farias (Medicinal Chemistry Research, 2018)

Evaluation of the serum virome in calves persistently infected with Pestivirus A, presenting or not presenting mucosal disease - Matheus N. Weber; Samuel P. Cibulski; Simone Silveira; Franciele M. Siqueira; Ana Cristina S. Mósena; Mariana S. da Silva; Juliana C. Olegário; Ana Paula M. Varela; Thaís F. Teixeira; Matheus V. Bianchi; David Driemeier; Saulo P. Pavarini; et al. (Virus Genes, 2018)

In situ phytoremediation characterization of heavy metals promoted by Hydrocotyle ranunculoides at Santa Bárbara stream, an anthropogenic polluted site in southern of Brazil - Carolina F. Demarco; Thays F. Afonso; Simone Pieniz; Maurízio S. Quadro; Flávio A. O. Camargo; Robson Andreazza (Environmental Science and Pollution Research, 2018)

Toward Improving Safety in Neurosurgery with an Active Handheld Instrument - Sara Moccia; Simone Foti; Arpita Routray; Francesca Prudente; Alessandro Perin; Raymond F. Sekula; Leonardo S. Mattos; Jeffrey R. Balzer; Wendy Fellows-Mayle; Elena De Momi; Cameron N. Riviere (Annals of Biomedical Engineering, 2018)

Surface properties, adhesion and biofilm formation on different surfaces by Scedosporium spp. and Lomentospora prolificans - Thaís P. Mello; Simone S. C. Oliveira; Susana Frasés; Marta H. Branquinha; André L. S. Santos (Biofouling, 2018)

Anacardic Acids from Cashew Nuts Prevent Behavioral Changes and Oxidative Stress Induced by Rotenone in a Rat Model of Parkinson’s Disease - Cybelle Façanha Barreto Medeiros-Linard; Belmira Lara da Silveira Andrade-da-Costa; Ricielle Lopes Augusto; Adriana Sereniki; Maria Teresa Sales Trevisan; Renata de Cássia Ribas Perreira; Francisco Thiago Correia de Souza; Glauber Ruda Feitoza Braz; Claudia Jacques Lagranha; Ivone Antônia de Souza; Almir Gonçalves Wanderley; Soraya S. Smailli; et al. (Neurotoxicity Research, 2018)

Detection and genetic characterization of classic human astroviruses in Brazil, 2010-2012 - Simone Guadagnucci Morillo; Adriana Luchs; Audrey Cilli; Rita de Cássia Compagnoli Carmona; Maria do Carmo S. T. Timenetsky (Archives of Virology, 2018)

Correction to: Cryptosporidium Spp. Contamination in Perna perna Mussels Destined for Human Consumption in Southeastern Rio de Janeiro, Brazil - A. L. Santos; L. T. F. de Oliveira; A. L. A. Souza; R. A. Hauser-Davis; S. G. De Simone (Bulletin of Environmental Contamination and Toxicology, 2018)

Cryptosporidium spp. Contamination in Perna perna Mussels Destined for Human Consumption in Southeastern Rio de Janeiro, Brazil - A. L. Santos; L. T. F. de Oliveira; A. L. A. Souza; R. A. Hauser-Davis; S. G. De Simone (Bulletin of Environmental Contamination and Toxicology, 2018)

Pre-culture in endothelial growth medium enhances the angiogenic properties of adipose-derived stem/stromal cells - Lucas E. B. Souza; Liziane R. Beckenkamp; Lays M. Sobral; Daianne M. C. Fantacini; Fernanda U. F. Melo; Josiane S. Borges; Andréia M. Leopoldino; Simone Kashima; Dimas Tadeu Covas (Angiogenesis, 2018)

A model-based assessment of the environmental impact of land-use change across scales in Southern Amazonia - Rüdiger Schaldach; Katharina H. E. Meurer; Hermann F. Jungkunst; Claas Nendel; Tobia Lakes; Florian Gollnow; Jan Göpel; Jens Boy; Georg Guggenberger; Robert Strey; Simone Strey; Thomas Berger; et al. (Regional Environmental Change, 2018)

Discovery of the first maize-infecting mastrevirus in the Americas using a vector-enabled metagenomics approach - Rafaela S. Fontenele; Dione M. T. Alves-Freitas; Pedro I. T. Silva; Josemar Foresti; Paulo. R. Silva; Márcio T. Godinho; Arvind Varsani; Simone G. Ribeiro (Archives of Virology, 2018)

Good Things in Small Packages: an Innovative Delivery Approach for Inhaled Insulin - James B. Fink; Lisa Molloy; John S. Patton; Valdecir Castor Galindo-Filho; Jacqueline de Melo Barcelar; Luciana Alcoforado; Simone Cristina Soares Brandão; Armèle Dornelas de Andrade (Pharmaceutical Research, 2017)

Spine Posture Influences Tactile Perceptual Sensitivity of the Trunk Dorsum - Shawn M. Beaudette; Simone G. V. S. Smith; Leah R. Bent; Stephen H. M. Brown (Annals of Biomedical Engineering, 2017)

Carnosic Acid Protects Mitochondria of Human Neuroblastoma SH-SY5Y Cells Exposed to Paraquat Through Activation of the Nrf2/HO-1Axis - Marcos Roberto de Oliveira; Alessandra Peres; Gustavo Costa Ferreira; Patrícia Fernanda Schuck; Clarissa S. Gama; Simone Morelo Dal Bosco (Molecular Neurobiology, 2017)

Gene networks for total number born in pigs across divergent environments - Lucas L. Verardo; Marcos S. Lopes; Pramod Mathur; Ole Madsen; Fabyano F. Silva; Martien A. M. Groenen; Egbert F. Knol; Paulo S. Lopes; Simone E. F. Guimarães (Mammalian Genome, 2017)

Can feedback analysis be used to uncover the physical origin of climate sensitivity and efficacy differences? - Vanessa S. Rieger; Simone Dietmüller; Michael Ponater (Climate Dynamics, 2017)

Genomic and antigenic relationships between two ‘HoBi’-like strains and other members of the Pestivirus genus - Ana Cristina S. Mósena; Samuel P. Cibulski; Matheus N. Weber; Simone Silveira; Mariana S. Silva; Fabiana Q. Mayer; Paulo M. Roehe; Cláudio W. Canal (Archives of Virology, 2017)

Genomic characterization of a bovine viral diarrhea virus subtype 1i in Brazil - Ana Cristina S. Mósena; Matheus N. Weber; Samuel P. Cibulski; Simone Silveira; Mariana S. Silva; Fabiana Q. Mayer; Cláudio W. Canal (Archives of Virology, 2017)

Can MHC ‐assortative partner choice promote offspring diversity? A new combination of MHC ‐dependent behaviours among sexes in a highly successful invasive mammal - Pablo S. C. Santos; Frank‐Uwe Michler; Simone Sommer (Molecular Ecology, 2017)
Sexual selection involving genetically disassortative mate choice is one of several evolutionary processes that can maintain or enhance population genetic variability. Examples of reproductive systems in which choosers (generally females) select mates depending on their major histocompatibility complex ( MHC ) genes have been reported for several vertebrate species. Notably, the role of MHC ‐dependent choice not in mating contexts, but in other kinds of social interactions such as in the establishment of complex social systems, has not yet drawn significant scientific interest and is virtually absent from the literature. We have investigated male and female MHC ‐dependent choice in an invasive population of North American raccoons ( Procyon lotor ) in Germany. Both male and female raccoons rely on olfaction for individual recognition. Males have an unusually complex social system in which older individuals choose unrelated younger ones to form stable male coalitions that defend territories and a monopoly over females. We have confirmed that females perform MHC ‐disassortative mate choice and that this behaviour fosters genetic diversity of offspring. We have also observed that males build coalitions by choosing male partners depending on their MHC , but in an assortative manner. This is the first observation of antagonistic MHC ‐dependent behaviours among sexes. We show that this is the only combination of MHC ‐dependent partner choice that leads to outbreeding. In the case of introduced raccoons, such behaviours can act together to promote the invasive potential of the species by increasing its adaptive genetic divergence.

Resistance to fire and the resilience of the woody vegetation of the “Cerradão” in the “Cerrado”–Amazon transition zone - Simone Matias Reis; Edmar Almeida de Oliveira; Fernando Elias; Letícia Gomes; Paulo S. Morandi; Beatriz Schwantes Marimon; Ben Hur Marimon Junior; Eder Carvalho das Neves; Bianca de Oliveira; Eddie Lenza (Brazilian Journal of Botany, 2017)

Characterization of carbon monoxide, methane and nonmethane hydrocarbons in emerging cities of Saudi Arabia and Pakistan and in Singapore - Barbara Barletta; Isobel J. Simpson; Nicola J. Blake; Simone Meinardi; Louisa K. Emmons; Omar S. Aburizaiza; Azhar Siddique; Jahan Zeb; Liya E. Yu; Haider A. Khwaja; Muhammad A. Farrukh; Donald R. Blake (Journal of Atmospheric Chemistry, 2017)

Biological aspects of Bemisia tabaci biotype B and the chemical causes of resistance in soybean genotypes - Simone S. Vieira; André L. Lourenção; José P. da Graça; Tatiani Janegitz; Mariana C. Salvador; Maria Cristina N. de Oliveira; Clara Beatriz Hoffmann-Campo (Arthropod-Plant Interactions, 2016)

Catalytic efficiencies of directly evolved phosphotriesterase variants with structurally different organophosphorus compounds in vitro - Moshe Goldsmith; Simone Eckstein; Yacov Ashani; Per Greisen; Haim Leader; Joel L. Sussman; Nidhi Aggarwal; Sergey Ovchinnikov; Dan S. Tawfik; David Baker; Horst Thiermann; Franz Worek (Archives of Toxicology, 2016)

Erratum to: Hierarchical modeling identifies novel lung cancer susceptibility variants in inflammation pathways among 10,140 cases and 11,012 controls - Darren R. Brenner; Paul Brennan; Paolo Boffetta; Christopher I. Amos; Margaret R. Spitz; Chu Chen; Gary Goodman; Joachim Heinrich; Heike Bickeböller; Albert Rosenberger; Angela Risch; Thomas Muley; et al. (Human Genetics, 2016)

Common carp Cyprinus carpio responses to sub-chronic exposure to perfluorooctanoic acid - Luisa Giari; Fabio Vincenzi; Simone Badini; Cristiana Guerranti; Bahram S. Dezfuli; Elisa A. Fano; Giuseppe Castaldelli (Environmental Science and Pollution Research, 2016)

Changes in Menidia beryllina Gene Expression and In Vitro Hormone-Receptor Activation After Exposure to Estuarine Waters Near Treated Wastewater Outfalls - Bryan J. Cole; Susanne M. Brander; Ken M. Jeffries; Simone Hasenbein; Guochun He; Michael S. Denison; Nann A. Fangue; Richard E. Connon (Archives of Environmental Contamination and Toxicology, 2016)

Odontocete occurrence in relation to changes in oceanography at a remote equatorial Pacific seamount - Simone Baumann‐Pickering; Jennifer S. Trickey; Sean M. Wiggins; Erin M. Oleson (Marine Mammal Science, 2016)
Seamounts are considered hot spots of biodiversity and can aggregate pelagic predators and their prey. Passive acoustic monitoring was conducted over 3 mo in 2012 to document the occurrence of odontocetes near a seamount chain in the central equatorial Pacific in relation to oceanographic changes over time. Beaked whale echolocation signals were most frequently encountered. The main beaked whale signal was an unknown type, BW 38, which resembled signals produced by Blainville's beaked whales. It had high occurrence during high sea surface temperature and low sea surface salinity. Cuvier's beaked whales were the second most detected. They had an opposite pattern and were encountered more often when sea surface temperature was low and net primary productivity was high. Risso's dolphins and short‐finned pilot whales had high acoustic densities, and echolocated predominantly at night. Risso's dolphins occurred more often during low sea surface height deviation. False killer whales were less frequently detected and mostly occurred during the day. Sperm whale detections were fewer than expected and associated with high chlorophyll a . Short duration Kogiidae encounters occurred on average every third day. These types of long‐term site studies are an informative tool to comparatively assess species composition, relative abundance, and relationship to oceanographic changes.

“Watching the Detectives” report of the general assembly of the EU project DETECTIVE Brussels, 24–25 November 2015 - Ruani N. Fernando; Umesh Chaudhari; Sylvia E. Escher; Jan G. Hengstler; Jürgen Hescheler; Paul Jennings; Hector C. Keun; Jos C. S. Kleinjans; Raivo Kolde; Laxmikanth Kollipara; Annette Kopp-Schneider; Alice Limonciel; et al. (Archives of Toxicology, 2016)

Severe Hyperhomocysteinemia Decreases Respiratory Enzyme and Na+-K+ ATPase Activities, and Leads to Mitochondrial Alterations in Rat Amygdala - Janaína Kolling; Emilene B. S. Scherer; Cassiana Siebert; Aline Longoni; Samanta Loureiro; Simone Weis; Letícia Petenuzzo; Angela T. S. Wyse (Neurotoxicity Research, 2016)

A matter of scale: apparent niche differentiation of diploid and tetraploid plants may depend on extent and grain of analysis - Bernhard Kirchheimer; Christoph C. F. Schinkel; Agnes S. Dellinger; Simone Klatt; Dietmar Moser; Manuela Winkler; Jonathan Lenoir; Marco Caccianiga; Antoine Guisan; Diego Nieto‐Lugilde; Jens‐Christian Svenning; Wilfried Thuiller; et al. (Journal of Biogeography, 2016)
Aim Emerging polyploids may depend on environmental niche shifts for successful establishment. Using the alpine plant Ranunculus kuepferi as a model system, we explore the niche shift hypothesis at different spatial resolutions and in contrasting parts of the species range. Location European Alps. Methods We sampled 12 individuals from each of 102 populations of R. kuepferi across the Alps, determined their ploidy levels, derived coarse‐grain (100 × 100 m) environmental descriptors for all sampling sites by downscaling WorldClim maps, and calculated fine‐scale environmental descriptors (2 × 2 m) from indicator values of the vegetation accompanying the sampled individuals. Both coarse and fine‐scale variables were further computed for 8239 vegetation plots from across the Alps. Subsequently, we compared niche optima and breadths of diploid and tetraploid cytotypes by combining principal components analysis and kernel smoothing procedures. Comparisons were done separately for coarse and fine‐grain data sets and for sympatric, allopatric and the total set of populations. Results All comparisons indicate that the niches of the two cytotypes differ in optima and/or breadths, but results vary in important details. The whole‐range analysis suggests differentiation along the temperature gradient to be most important. However, sympatric comparisons indicate that this climatic shift was not a direct response to competition with diploid ancestors. Moreover, fine‐grained analyses demonstrate niche contraction of tetraploids, especially in the sympatric range, that goes undetected with coarse‐grained data. Main conclusions Although the niche optima of the two cytotypes differ, separation along ecological gradients was probably less decisive for polyploid establishment than a shift towards facultative apomixis, a particularly effective strategy to avoid minority cytotype exclusion. In addition, our results suggest that coarse‐grained analyses overestimate niche breadths of widely distributed taxa. Niche comparison analyses should hence be conducted at environmental data resolutions appropriate for the organism and question under study.

“Unfocus” on foc.us: commercial tDCS headset impairs working memory - Laura Steenbergen; Roberta Sellaro; Bernhard Hommel; Ulman Lindenberger; Simone Kühn; Lorenza S. Colzato (Experimental Brain Research, 2016)
In this study, we tested whether the commercial transcranial direct current stimulation (tDCS) headset foc.us improves cognitive performance, as advertised in the media. A single-blind, sham-controlled, within-subject design was used to assess the effect of online and off-line foc.us tDCS—applied over the prefrontal cortex in healthy young volunteers ( n = 24) on working memory (WM) updating and monitoring. WM updating and monitoring, as assessed by means of the N -back task, is a cognitive-control process that has been shown to benefit from interventions with CE-certified tDCS devices. For both online and off-line stimulation protocols, results showed that active stimulation with foc.us , compared to sham stimulation, significantly decreased accuracy performance in a well-established task tapping WM updating and monitoring. These results provide evidence for the important role of the scientific community in validating and testing far-reaching claims made by the brain training industry.

Altered relaxin family receptors RXFP1 and RXFP3 in the neocortex of depressed Alzheimer’s disease patients - Jasinda H. Lee; Shu Qing Koh; Simone Guadagna; Paul T. Francis; Margaret M. Esiri; Christopher P. Chen; Peter T.-H. Wong; Gavin S. Dawe; Mitchell K. P. Lai (Psychopharmacology, 2016)

Breeding on the leading edge of a northward range expansion: differences in morphology and the stress response in the arctic Gambel’s white-crowned sparrow - Jesse S. Krause; Helen E. Chmura; Jonathan H. Pérez; Lisa N. Quach; Ashley Asmus; Karen R. Word; Michaela A. McGuigan; Shannan K. Sweet; Simone L. Meddle; Laura Gough; Natalie Boelman; John C. Wingfield (Oecologia, 2016)

Epigenetic mechanisms underlying arsenic-associated lung carcinogenesis - Simone G. J. van Breda; Sandra M. H. Claessen; Ken Lo; Marcel van Herwijnen; Karen J. J. Brauers; Sofia Lisanti; Daniël H. J. Theunissen; Danyel G. J. Jennen; Stan Gaj; Theo M. C. M. de Kok; Jos C. S. Kleinjans (Archives of Toxicology, 2015)

The Impact of Trampling on Reef Macrobenthos in Northeastern Brazil: How Effective are Current Conservation Strategies? - Gleice S. Santos; Douglas C. Burgos; Simone M. A. Lira; Ralf Schwamborn (Environmental Management, 2015)

Antarctic beaked whale echolocation signals near South Scotia Ridge - Jennifer S. Trickey; Simone Baumann‐Pickering; John A. Hildebrand; Maria Vanesa Reyes Reyes; Mariana Melcón; Miguel Iñíguez (Marine Mammal Science, 2015)

Stewardship to tackle global phosphorus inefficiency: The case of Europe - Paul J. A. Withers; Kimo C. van Dijk; Tina-Simone S. Neset; Thomas Nesme; Oene Oenema; Gitte H. Rubæk; Oscar F. Schoumans; Bert Smit; Sylvain Pellerin (Ambio, 2015)

Geographic variation in polyandry of the Eastern Honey Bee, Apis cerana, in Thailand - D. S. DeFelice; C. Ross; M. Simone-Finstrom; N. Warrit; D. R. Smith; M. Burgett; P. Sukumalanand; O. Rueppell (Insectes Sociaux, 2015)

Endocannabinoids produced upon action potential firing evoke a Cl− current via type-2 cannabinoid receptors in the medial prefrontal cortex - Femke S. den Boon; Pascal Chameau; Kas Houthuijs; Simone Bolijn; Nicolina Mastrangelo; Chris G. Kruse; Mauro Maccarrone; Wytse J. Wadman; Taco R. Werkman (Pflügers Archiv - European Journal of Physiology, 2014)

The hypotensive effect of the ruthenium complex [Ru(terpy)(bdq)NO]3+ is higher in male than in female spontaneously hypertensive rats (SHR) - Simone R. Potje; Mariana C. Hildebrand; Felipe C. Munhoz; Jéssica A. Troiano; Ariana A. F. Pereira; Ana Claúdia M. S. Nakamune; Roberto S. da Silva; Lusiane M. Bendhack; Cristina Antoniali (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Linalool and linalool complexed in β-cyclodextrin produce anti-hyperalgesic activity and increase Fos protein expression in animal model for fibromyalgia - Simone S. Nascimento; Enilton A. Camargo; Josimari M. DeSantana; Adriano A. S. Araújo; Paula P. Menezes; Waldecy Lucca-Júnior; Ricardo L. C. Albuquerque-Júnior; Leonardo R. Bonjardim; Lucindo J. Quintans-Júnior (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

The state of the art of Xyalidae (Nematoda, Monhysterida) with reference to the Brazilian records - Virág Venekey; Paula F. Gheller; Tatiana F. Maria; Marco C. Brustolin; Noelia Kandratavicius; Danilo C. Vieira; Simone Brito; Guilherme S. Souza; Gustavo Fonseca (Marine Biodiversity, 2014)

A family history questionnaire improves detection of women at risk for hereditary gynecologic cancer: a pilot study - Margot M. Koeneman; Arnold-Jan Kruse; Simone J. S. Sep; Cynthia S. Gubbels; Brigitte F. M. Slangen; Toon van Gorp; Alberto Lopes; Encarna Gomez-Garcia; Roy F. P. M. Kruitwagen (Familial Cancer, 2014)

Early postnatal, but not late, exposure to chemical ambient pollutant 1,2-naphthoquinone increases susceptibility to pulmonary allergic inflammation at adulthood - Karen T. Santos; Juliana Florenzano; Leandro Rodrigues; Rodolfo R. Fávaro; Fernanda F. Ventura; Marcela G. Ribeiro; Simone A. Teixeira; Heloisa H. A. Ferreira; Susan D. Brain; Amílcar S. Damazo; Telma M. Zorn; Niels O. Câmara; et al. (Archives of Toxicology, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Recurrent Varicella following Steroids and Fingolimod in a Multiple Sclerosis Patient - D. Ferraro; S. De Biasi; F. Vitetta; A. M. Simone; L. Federzoni; V. Borghi; A. Cossarizza; P. F. Nichelli; P. Sola (Journal of Neuroimmune Pharmacology, 2013)

Molecular and biological characterization of corchorus mottle virus, a new begomovirus from Brazil - Rosana Blawid; Rafaela S. Fontenele; Cristiano Lacorte; Simone G. Ribeiro (Archives of Virology, 2013)

Disturbances, elevation, topography and spatial proximity drive vegetation patterns along an altitudinal gradient of a top biodiversity hotspot - Pedro V. Eisenlohr; Luciana F. Alves; Luís Carlos Bernacci; Maíra C. G. Padgurschi; Roseli B. Torres; Eduardo M. B. Prata; Flavio Antonio M. dos Santos; Marco Antônio Assis; Eliana Ramos; André Luís C. Rochelle; Fernando R. Martins; Mariana C. R. Campos; et al. (Biodiversity and Conservation, 2013)

Bioactives and nutraceutical phytochemicals naturally occurring in virgin olive oil. The case study of the Nocellara del Belice Italian olive cultivar - F. Ranalli; A. Ranalli; S. Contento; M. Casanovas; M. Antonucci; G. Di Simone (Natural Product Research, 2013)

Implementation, Testing and Pilot Clinical Evaluation of Superelastic Splints that Decrease Joint Stiffness - Simone Pittaccio; L. Garavaglia; S. Viscuso; E. Beretta; S. Strazzer (Annals of Biomedical Engineering, 2013)

High Resolution Simulation of the Variability of Surface Energy Balance Fluxes Across Central London with Urban Zones for Energy Partitioning - Thomas Loridan; Fredrik Lindberg; Oriol Jorba; Simone Kotthaus; Susanne Grossman-Clarke; C. S. B. Grimmond (Boundary-Layer Meteorology, 2013)

Hierarchical modeling identifies novel lung cancer susceptibility variants in inflammation pathways among 10,140 cases and 11,012 controls - Darren R. Brenner; Paul Brennan; Paolo Boffetta; Christopher I. Amos; Margaret R. Spitz; Chu Chen; Gary Goodman; Joachim Heinrich; Heike Bickeböller; Albert Rosenberger; Angela Risch; Thomas Muley; et al. (Human Genetics, 2013)

Mobile Farm Clinic Outreach to Address Health Conditions Among Latino Migrant Farmworkers in Georgia - John S. Luque; Carlos Reyes-Ortiz; Prasen Marella; Angelica Bowers; Viral Panchal; Lisa Anderson; Simone Charles (Journal of Agromedicine, 2012)

Tuberculosis: Finding a New Potential Antimycobacterium Derivative in a Aldehyde–Arylhydrazone–Oxoquinoline Series - Fernanda C. Santos; Helena C. Castro; Maria Cristina S. Lourenço; Paula A. Abreu; Pedro N. Batalha; Anna C. Cunha; Guilherme S. L. Carvalho; Carlos R. Rodrigues; Cid A. Medeiros; Simone D. Souza; Vitor F. Ferreira; Maria C. B. V. Souza (Current Microbiology, 2012)

Asbestos Risk: From Raw Material to Waste Management: The Italian Experience - F. Paglietti; S. Malinconico; V. Di Molfetta; S. Bellagamba; F. Damiani; F. Gennari; P. De Simone; F. Sallusti; M. Giangrasso (Critical Reviews in Environmental Science and Technology, 2012)

Latitudinal variation in blue tit and great tit nest characteristics indicates environmental adjustment - Mark C. Mainwaring; Ian R. Hartley; Stuart Bearhop; Kaat Brulez; Christopher R. du Feu; Gerald Murphy; Kate E. Plummer; Simone L. Webber; S. James Reynolds; D. Charles Deeming (Journal of Biogeography, 2012)
Aim The laying of eggs and the building of a nest structure to accommodate them are two of the defining characteristics of members of the class Aves. Nest structures vary considerably across avian taxa and for many species the structure of the completed nest can have important consequences both for parents and their offspring. While nest characteristics are expected to vary adaptively in response to environmental conditions, large‐scale spatial variation in nest characteristics has been largely overlooked. Here, we examine the effects of latitudinal variation in spring temperatures on nest characteristics, including insulatory properties, and reproductive success of blue tits, Cyanistes caeruleus , and great tits, Parus major . Location Great Britain. Methods Nests and reproductive data were collected from seven study sites, spread over 5° of latitude. The nest insulatory properties were then determined before the nests were separated into nest base material and cup lining material. Results As spring temperatures increased with decreasing latitude, the mass of the nest base material did not vary in either species, while the mass of the cup lining material and nest insulatory properties decreased in both species. This suggests that in response to increasing temperatures the breeding female reduces the mass of the cup lining material, thereby maintaining an appropriate microclimate for incubating and brooding. The mean first egg date of both species advanced with decreasing latitude and increasing spring temperatures, although clutch size and brood size at hatching and fledging did not vary. Main conclusions This is the first study to demonstrate that the nest‐construction behaviour of birds varies in response to large‐scale spatial variation in ambient temperatures. Therefore, nest composition reliably indicates environmental conditions and we suggest that studies of nest structure may be sentinels for the early signs of rapid climate change.

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

Foraging activity of bumblebees (Bombus terrestris L.) on Bt-expressing eggplants - Salvatore Arpaia; Antonio De Cristofaro; Emilio Guerrieri; Simone Bossi; Francesco Cellini; Grazia M. Di Leo; Giacinto S. Germinara; Luigi Iodice; Massimo E. Maffei; Angelo Petrozza; Raffaele Sasso; Silvia Vitagliano (Arthropod-Plant Interactions, 2011)

Unraveling new genes associated with seed development and metabolism in Bixa orellana L. by expressed sequence tag (EST) analysis - Virgínia L. F. Soares; Simone M. Rodrigues; Tahise M. de Oliveira; Talisson O. de Queiroz; Lívia S. Lima; Braz T. Hora-Júnior; Karina P. Gramacho; Fabienne Micheli; Júlio C. M. Cascardo; Wagner C. Otoni; Abelmon S. Gesteira; Marcio G. C. Costa (Molecular Biology Reports, 2011)

Detection of cross-infection associated to a Brazilian PCR-ribotype of Clostridium difficile in a university hospital in Rio de Janeiro, Brazil - Ilana T. Balassiano; Joaquim dos Santos-Filho; Juliana M. Vital-Brazil; Simone A. Nouér; Claudia R. C. Souza; Jon S. Brazier; Eliane de O. Ferreira; Regina M. C. P. Domingues (Antonie van Leeuwenhoek, 2011)

Reworking the idea of chestnut ( Castanea sativa Mill.) cultivation in Roman times: New data from ancient Campania - G. Di Pasquale; E. Allevato; E. Russo Ermolli; S. Coubray; C. Lubritto; F. Marzaioli; M. Yoneda; K. Takeuchi; Y. Kano; S. Matsuyama; G. F. De Simone (Plant Biosystems, 2010)

Diagenesis of the Khuff Formation (Permian–Triassic), northern United Arab Emirates - Simone Fontana; Fadi H. Nader; Sadoon Morad; Andrea Ceriani; Ihsan S. Al-Aasm (Arabian Journal of Geosciences, 2010)

Indirect effects of a key ecosystem engineer alter survival and growth of foundation coral species - Jada-Simone S. White; James L. O'Donnell (Ecology, 2010)
Stegastes nigricans , a “farmerfish” that cultivates algal turf and defends territories from grazers and other intruders, can affect coral indirectly due to increased competition with farmed algal turf and/or reduced predation resulting from territorial aggression directed at corallivores. To investigate the indirect effects of this key ecosystem engineer on coral mortality and growth, we transplanted caged and exposed fragments of four coral species to patch reefs in French Polynesia on which we manipulated the presence of S. nigricans and turf, and to reefs naturally devoid of S. nigricans . Reef access was two to four times higher for herbivorous fishes, and two times higher for corallivorous fishes, when S. nigricans was removed, indicating that reef access is reduced for two important guilds of fishes when S. nigricans is present. Stegastes ' territoriality indirectly benefited delicate acroporids ( Montipora floweri and Acropora striata ), yielding a twofold to fivefold reduction in skeletal loss due to lower predation frequencies in the presence of S. nigricans . Three corals, A. striata , M. floweri , and especially Porites australiensis , suffered mortality due to overgrowth significantly more frequently in the presence of farmed turf, but Pocillopora verrucosa did not. Algal abundance predicted the frequency of overgrowth for only A. striata and P. australiensis . M. floweri were more likely to be overgrown when exposed (uncaged) in the presence of S. nigricans , suggesting an interaction modification, in this case that initial predation increased susceptibility to competition with turf. In this community, the presence of S. nigricans may increase algal overgrowth of massive Porites by facilitating its turf competitors and simultaneously reduce predation of branching corals through territorial exclusion of corallivores. These indirect interactions may underlie previously documented community transitions from disturbance‐resistant massive coral to recovering branching corals within S. nigricans territories.

Epidemiology of influenza-associated hospitalization in adults, Toronto, 2007/8 - S. P. Kuster; S. Drews; K. Green; J. Blair; I. Davis; J. Downey; R. Fowler; K. Katz; S. Lapinsky; D. McRitchie; J. Pataki; J. Powis; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Saccharomyces cerevisiae strain UFMG 905 protects against bacterial translocation, preserves gut barrier integrity and stimulates the immune system in a murine intestinal obstruction model - Simone V. Generoso; Mirelle Viana; Rosana Santos; Flaviano S. Martins; José A. N. Machado; Rosa M. E. Arantes; Jacques R. Nicoli; Maria I. T. D. Correia; Valbert N. Cardoso (Archives of Microbiology, 2010)

Microsomal epoxide hydrolase expression in the endometrial uterine corpus is regulated by progesterone during the menstrual cycle - Simone L. Popp; Ina S. Abele; Miriam B. Buck; Matthias B. Stope; Leen J. Blok; Payman Hanifi-Moghaddam; Curt W. Burger; Peter Fritz; Cornelius Knabbe (Journal of Molecular Histology, 2010)

Stratospheric ozone during the arctic winter: Brewer measurements in Ny-Ålesund - C. Rafanelli; S. De Simone; A. Damiani; C. Lund Myhre; K. Edvardsen; T. Svenoe; E. Benedetti (International Journal of Remote Sensing, 2009)

Karyotypic and molecular polymorphisms in Ctenomys torquatus (Rodentia: Ctenomyidae): taxonomic considerations - Fabiano A. Fernandes; Gislene L. Gonçalves; Simone S. F. Ximenes; Thales R. O. de Freitas (Genetica, 2009)

Net Ecosystem Metabolism and Nonconservative Fluxes of Organic Matter in a Tropical Mangrove Estuary, Piauí River (NE of Brazil) - Marcelo F. L. Souza; Viviane R. Gomes; Simone S. Freitas; Regina C. B. Andrade; Bastiaan Knoppers (Estuaries and Coasts, 2009)

Phylogenetic Placement of Pentatomid Stink Bug Gut Symbionts - Simone S. Prado; Rodrigo P. P. Almeida (Current Microbiology, 2009)

Differentiation in DNA fingerprinting among species of the genus Acer L. in Campania (Italy) - C. Guarino; S. Santoro; L. De Simone; G. Cipriani; R. Testolin (Plant Biosystems, 2008)

Influence of sex steroid hormones on spatial memory in a songbird - Zoë G. Hodgson; Simone L. Meddle; Julian K. Christians; Todd S. Sperry; Susan D. Healy (Journal of Comparative Physiology A, 2008)

A New Missense Mutation Found in the FLNA Gene in a Family with Bilateral Periventricular Nodular Heterotopia (BPNH) Alters the Splicing Process - Simone S. Tsuneda; Fabio R. Torres; Maria A. Montenegro; Marilisa M. Guerreiro; Fernando Cendes; Iscia Lopes-Cendes (Journal of Molecular Neuroscience, 2008)

Amino acid uptake among wide-ranging moss species may contribute to their strong position in higher-latitude ecosystems - Eveline J. Krab; Johannes H. C. Cornelissen; Simone I. Lang; Richard S. P. van Logtestijn (Plant and Soil, 2008)

Synthesis, in vitro and in vivo characterization of 64Cu(I) complexes derived from hydrophilic tris(hydroxymethyl)phosphane and 1,3,5-triaza-7-phosphaadamantane ligands - Simone Alidori; Giancarlo Gioia Lobbia; Grazia Papini; Maura Pellei; Marina Porchia; Fiorenzo Refosco; Francesco Tisato; Jason S. Lewis; Carlo Santini (JBIC Journal of Biological Inorganic Chemistry, 2008)

Identification and characterization of proteases from skin mucus of tambacu, a Neotropical hybrid fish - C. M. C. Salles; P. Gagliano; S. A. T. Leitão; J. B. Salles; H. L. M. Guedes; V. P. F. Cassano; S. Giovanni De-Simone (Fish Physiology and Biochemistry, 2007)

Survival and growth of two heterotrophic hydrothermal vent archaea, Pyrococcus strain GB-D and Thermococcus fumicolans, under low pH and high sulfide concentrations in combination with high temperature and pressure regimes - Virginia P. Edgcomb; Stephen J. Molyneaux; Simone Böer; Carl O. Wirsen; Mak Saito; Michael S. Atkins; Karen Lloyd; Andreas Teske (Extremophiles, 2007)

Localization of granulatimide alkaloids in the tissues of the ascidian Didemnum granulatum - Mirna H. R. Seleghim; Simone P. de Lira; Patrícia T. Campana; Roberto G. S. Berlinck; Marcio R. Custódio (Marine Biology, 2007)

Regulation of ventilation in the caiman (Caiman latirostris): effects of inspired CO2 on pulmonary and upper airway chemoreceptors - Glenn J. Tattersall; Denis V. de Andrade; Simone P. Brito; Augusto S. Abe; William K. Milsom (Journal of Comparative Physiology B, 2006)

Osteopontin expression in coculture of differentiating rat fetal skeletal fibroblasts and myoblasts - Renata O. Pereira; Simone N. Carvalho; Ana Carolina Stumbo; Carlos A. B. Rodrigues; Luis Critóvão Porto; Anibal S. Moura; Laís Carvalho (In Vitro Cellular & Developmental Biology - Animal, 2006)

OSTEOPONTIN EXPRESSION IN COCULTURE OF DIFFERENTIATING RAT FETAL SKELETAL FIBROBLASTS AND MYOBLASTS - RENATA O. PEREIRA; SIMONE N. CARVALHO; ANA CAROLINA STUMBO; CARLOS A. B. RODRIGUES; LUIS CRITÓVÃO PORTO; ANIBAL S. MOURA; LAÍS CARVALHO (In Vitro Cellular & Developmental Biology - Animal, 2006)

Paleolimnological investigations of anthropogenic environmental change in Lake Tanganyika: IX. Summary of paleorecords of environmental change and catchment deforestation at Lake Tanganyika and impacts on the Lake Tanganyika ecosystem - Andrew S. Cohen; Manuel R. Palacios-Fest; Emma S. Msaky; Simone R. Alin; Brent McKee; Catherine M. O’Reilly; David L. Dettman; Hudson Nkotagu; Kiram E. Lezzar (Journal of Paleolimnology, 2005)

Paleolimnological investigations of anthropogenic environmental change in Lake Tanganyika: IV. Lacustrine paleoecology - Manuel R. Palacios-Fest; Simone R. Alin; Andrew S. Cohen; Brandon Tanner; Heather Heuser (Journal of Paleolimnology, 2005)

Paleolimnological investigations of anthropogenic environmental change in Lake Tanganyika: II. Geochronologies and mass sedimentation rates based on 14C and 210Pb data - Brent A. McKee; Andrew S. Cohen; David L. Dettman; Manuel R. Palacios-Fest; Simone R. Alin; Gerard Ntungumburanye (Journal of Paleolimnology, 2005)

Paleolimnological investigations of anthropogenic environmental change in Lake Tanganyika: I. An introduction to the project - Andrew S. Cohen; Manuel R. Palacios-Fest; James McGill; Peter W. Swarzenski; Dirk Verschuren; Robert Sinyinza; Tharcisse Songori; Bombi Kakagozo; Mutanga Syampila; Catherine M. O’Reilly; Simone R. Alin (Journal of Paleolimnology, 2005)

Visual feedback reduces bimanual coupling of movement amplitudes, but not of directions - Simone Cardoso de Oliveira; Sbastien Barthlmy (Experimental Brain Research, 2005)

INFLUENCE OF SERUM ON ADULT AND FETAL DERMAL FIBROBLAST MIGRATION, ADHESION, AND COLLAGEN EXPRESSION - HALLIE E. BRINK; SIMONE S. STALLING; STEVEN B. NICOLL (In Vitro Cellular & Developmental Biology - Animal, 2005)

Phylogenetic Timing of the Fish-Specific Genome Duplication Correlates with the Diversification of Teleost Fish - Simone Hoegg; Henner Brinkmann; John S. Taylor; Axel Meyer (Journal of Molecular Evolution, 2004)

Titi monkeys (Callicebus spp., Atelidae: Platyrrhini) in the Brazilian state of Rondônia - Stephen F. Ferrari; Simone Iwanaga; Mariluce R. Messias; Eleildon M. Ramos; Paulo C. S. Ramos; Ernesto H. da Cruz Neto; Paulo E. G. Coutinho (Primates, 2000)

Zoogeography of Chiropotes albinasus (Platyrrhini, Atelidae) in Southwestern Amazonia - Stephen F. Ferrari; Simone Iwanaga; Paulo E. G. Coutinho; Mariluce R. Messias; Ernesto H. Cruz Neto; Eleildon M. Ramos; Paulo C. S. Ramos (International Journal of Primatology, 1999)

Effects of Landscape Disturbance on Animal Communities in Lake Tanganyika, East Africa - Simone R. Alin; Andrew S. Cohen; Roger Bills; Masta Mukwaya Gashagaza; Ellinor Michel; Jean‐Jacques Tiercelin; Koen Martens; Peter Coveliers; Sima Keita Mboko; Kelly West; Michael Soreghan; Sona Kimbadi; et al. (Conservation Biology, 1999)
Watershed deforestation, road building, and other anthropogenic activities result in sediment inundation of lacustrine habitats. In Lake Tanganyika, this threatens the survival of many rock‐dwelling species by altering the structure and quality of rocky habitats. We investigated the relationship between habitat quality, as related to watershed disturbance intensity, and the biodiversity of faunal communities at three rocky littoral sites of low, moderate, and high disturbance. Turbidity measurements and other environmental observations confirmed that our lake sites represented a gradient of disturbance conditions. We documented differences in species density (number of species per constant area or time), species richness, abundance, and trophic ecology for fishes, molluscs, and ostracods. Fish censuses were performed by scuba divers at 1–20 m and by remotely operated vehicle (ROV) at 40–80 m. In the fish surveys, abundance, species density and richness, and herbivory reached their maxima at intermediate water depths. The depth range of herbivores, however, was restricted at higher‐disturbance sites. The ROV fish surveys at the high‐disturbance site showed high species richness despite low species density and abundance, and piscivores were proportionally more prevalent than in all other surveys. Molluscs censused by diver quadrats and sieve samples showed decreasing species richness and species density (sieve samples only) with increasing disturbance and no significant abundance trend. Ostracod species richness was similar between low‐ and moderate‐disturbance sites but was markedly lower at the high‐disturbance site (species density and abundance data were not available). Our faunal analyses suggest that all three taxonomic groups are negatively affected by sediment inundation but may have varying response thresholds to disturbance. Further, this study emphasized the utility of using complementary survey techniques to monitor and ultimately manage biodiversity in complex freshwater ecosystems.

Intracellular localization of rotaviral proteins - Simone C. Richardson; Linda E. Mercer; S. Sonza; I. H. Holmes (Archives of Virology, 1986)